Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Freeze-thaw-induced greenhouse gas emissions from a Mollisol agroecosystem: Microbial and edaphic regulation under long-term agricultural management - Dan-Dan Wang; Shan-Shan Dai; Peng He; Zhi-Ming Zhang; Jian-Ying Zhou; Ming-Hui Liu; Shi-Xiu Zhang; Lu-Jun Li (Soil and Tillage Research, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Unlocking the hidden carbon pool: Refractory organic matter drives superior chain elongation in sludge alkaline fermentation liquid - Dingkang Qian; Ziming Xu; Mengjiao Yuan; Zhen Li; Qian Zhu; Ming Peng; Jianyu Gong; Jiakuan Yang; Jingping Hu; Huijie Hou (Water Research, 2026)

Large-scale shaking table test study on dynamic response, failure characteristics, and seismic mechanisms of soft-hard interbedded bedding rock slopes reinforced by pile-anchor composite structure - Fei Zhao; Zhenming Shi; Bo Li; Songbo Yu; Ming Peng; Jianfeng Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

MDA5 associates with MAVS and its splicing variant in the antiviral response of large yellow croaker Larimichthys crocea - Ying Li; Yi Fan Zhang; Xia Ming Chen; Qiang Ma; Jiao Nan Zhang; Xiao Mei Huang; Jing Xuan Li; Yu Xuan Zhu; Tuan Yu Guo; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

An enhanced SPH framework to simulate dynamic motion of soil-rock mixtures considering discontinuity contact - Chengzhi Xia; Zhenming Shi; Ming Peng; Jian He; Hang Li; Limin Zhang (Computers and Geotechnics, 2026)

Quantifying the effects of lift-up building morphology on pedestrian-level wind and comfort in dense urban arrays: A data-driven study - Shuqi Peng; Cheuk Ming Mak; Wenxin Li; Lan Chen; Shengbiao Li; Jinyu Li; Ziqing Zhou; Fei Yan; Chang Liu; Yi He (Sustainable Cities and Society, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Revealing the dominant role of pectin in softening texture and enhancing drying behaviors of grapes after cold plasma pretreatment - An-An Zhang; Fan Yang; Ming-Qiang Xu; Wei-Peng Zhang; Jin-Run Li; Hai-Bin Yang; Jing-Shou Zhang; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Microbial community reshape and TTMP enhancement in daqu via targeted bioaugmentation of Bacillus velezensis and Bacillus licheniformis - Mai Cheng; Xuanchen Li; Jiang Long; Feiyan Wu; Ming Jiang; Chao Wang; Ankang Que; Xuelian Huang; Xiaodong Peng; Wangni Meng; Jianli Zhou; Jianmeng Zhu (Food Microbiology, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Constructing a PANI/MnO2-x@PP photothermal membrane for high-performance solar-driven water purification and energy harvesting - Jian Peng; Hao Li; Yuxin Wang; Yifan Ma; Guozhang Zhu; Jinhong Huang; Yiping Liu; Ming Lu (Desalination, 2026)

Hierarchically structured superamphiphobic radiative cooling fabric for personal thermal management - Wen-Jing Zhao; Chao-Hua Xue; Xiao-Jing Guo; Jing-Jing Peng; Li Wan; Yan Yang; Shi-Hang Lv; Jin-Yu Wang; Teng-Xin Wang; Ming-Wei Chang (Chemical Engineering Journal, 2026)

Discriminating global ore deposit genetic types using chalcopyrite trace elements: Insights from interpretable machine learning - Hong-Kai Li; Ming-Yu Cao; Ben Qin; Peng-Fei Wang; Le Wang (Chemical Geology, 2026)

Chemical constituents from Micromeria biflora and their chemotaxonomic significance - Chen Peng; Xing-Li Zhang; Deng-Li Xiong; Fei-Yan Zhao; Kun Xie; Hong-Ping He; Ming-Ming Li (Biochemical Systematics and Ecology, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Molecular Mechanism of Absorption, Transport and Metabolic Transformation of Astaxanthin in Aquatic Animals - Huakang Peng; Yihui Du; Qianwen Ding; Dongdong Du; Ruyue Dong; Chao Ran; Zhen Zhang; Yuanyuan Yao; Hui Liang; Ming Li; Nan Wang; Yalin Yang; et al. (Reviews in Aquaculture, 2026)
The global astaxanthin market reached $1.69 billion in 2024, with 47% directed to aquafeed—yet the molecular basis of its absorption, metabolism, deposition, and storage in aquatic organisms remains incompletely resolved. A deeper understanding of these mechanisms will help optimize feed formulations, enhance astaxanthin bioavailability, and improve economic efficiency in aquaculture. This study investigates the absorption mechanisms of astaxanthin mediated by intestinal lipid transporters (SR‐B1, CD36, NPC1L1) and its utilization/deposition in different tissues and organs. It reviews the latest research progress on major absorption pathways, metabolic processes, and storage forms of astaxanthin in aquatic organisms, analyzes key factors affecting its utilization efficiency, and discusses potential future research directions to provide a scientific basis and theoretical support for aquaculture practices.

A unified 3D SPH framework for simulating the landslide-damming-breaching-flood cascading hazards - Shuang Li; Ming Peng; Zhenming Shi; Hongchao Zheng; Chengzhi Xia; Maomao Liu; Yan Zhu (Engineering Geology, 2026)

High-throughput prediction of the lowest triplet excitation energies in organic photovoltaic acceptors using physics-guided excess-factor-corrected fragment descriptors - Lei Cheng; Rui-Cheng Qin; Peng Xie; Ming-Yang Li; Yue Ren; Guang-Yan Sun (Chemical Engineering Journal, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Simultaneous interlayer engineering and interface modulation of MXene via zirconium nanoclusters for enhanced lithium storage - Jiajia Sun; Zehao Zhang; Peng Yang; Xianghui Hu; Kailiang Ming; Xiaoming Chen; Yong Zhao; Linfeng Fei; Haibo Li; Zhouyang Zhang (Chemical Engineering Journal, 2026)

Lignin-tailored synergistic catalyst with cobalt single-atom and zinc clusters dual-site for conversion of hemicellulose to lactic acid - Chen-Xi Li; Qian Ren; Feng Peng; Ming-Fei Li (Bioresource Technology, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Root oxygen governs dryland ecosystem stability - Dongliang Han; Lei Ding; Guolong Zhang; Jianping Huang; Li Fu; Ming Peng; Changyu Li; Xiaoyue Liu (Plant and Soil, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Unexpected V-shaped temperature dependence of methane fluxes informing its sources in a megacity of China - Ruilin Zhang; Yibo Huangfu; Bin Yuan; Xiaoxiao Zhang; Xianjun He; Thomas Karl; Yang Ding; Hongjuan Li; Kyung-Eun Min; Ying Xiong; Xiao-Bing Li; Zhe Peng; et al. (Science Bulletin, 2026)

Robust monitoring design for CO2-flue gas co-storage in saline aquifers under geological heterogeneity - Yuanming Li; Bei Li; Shuangxing Liu; Ming Xue; Xingchun Li; Peng Wu (Process Safety and Environmental Protection, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Electrochemical chlorination byproducts (ECBPs): A potential blind spot in electrochemical treatment of waste activated sludge - Dingkang Qian; Qian Zhu; Mengjiao Yuan; Ziming Xu; Jinwen Zhang; Na Li; Ming Peng; Liqiong Cao; Jianyu Gong; Jingping Hu; Huijie Hou; Jiakuan Yang; et al. (Journal of Hazardous Materials, 2026)

Bio-based fiber electrodes via continuous interfacial polyelectrolyte complexation for electro-optical sensing textiles - Lihong Geng; Wenping Zhang; Zhengxi Hao; Xinyu Gan; Yuhang Li; Yang Ming; Shuo Shi; Xiangfang Peng (Chemical Engineering Journal, 2026)

Low enthalpy 3D evaporators coupled with auxiliary thermal management for rapid solar evaporation - Ze-Ming Huang; Hong-Yu Chu; Ye-Tong Liu; Xiang-Jing Mo; Jing Li; Chong-Chen Wang; Peng Wang; Xiao-Hong Yi (Chemical Engineering Journal, 2026)

Decoding, Mapping, and Designing: A New Paradigm for Harnessing Umbilical Cord Mesenchymal Stem Cell Heterogeneity in Obstetric Precision Therapy - Zhang-Lu An; Zhi-Ming Wang; Wen-Hao Zhao; Li-Juan Peng; Er-Meng Gao (Stem Cell Reviews and Reports, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

UAV-based crop pest and disease monitoring: A review of multi-source sensing and intelligent methods - Jie Guo; Jin-Hai Li; Le Dong; Shun-Yu Wang; Guang-Yue Wu; Yu-Peng Zhang; Chang-Yong Tao; De-Hua Gao; Shu-Ming Yang; Yu-Tan Wang (Computers and Electronics in Agriculture, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

Drivers of the temporal and spatial variation in gully growth rates in Northeast China - Yanru Wen; Jingyue Li; Zhufeng Wang; Karl Auerswald; Peter Fiener; Wim Cornelis; Peng Qi; Ting-yong Li; Xinhua Peng; Liming Ye; Wenbin Wu; Ming Jiang; et al. (Science Bulletin, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Freeze-thaw cycles threaten high-altitude cold-region rock slopes stability: Advances in SPH simulation - Chengzhi Xia; Zhenming Shi; Hang Li; Ming Peng; Limin Zhang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Pulsed vacuum drying remodels the texture of dried jujube by regulating low-methylesterified pectin and Ca2+-mediated egg-box structures - Xiao-Xiao Niu; Ming-Qiang Xu; Jozef Mravec; Wei-Peng Zhang; Li-Zhen Deng; Guo-gang Chen; Wei-qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Homocysteine-induced bone formation dysfunction reversed by icariin via the AKT/FOXO1 signaling pathway - Suzhen Chao; Yunying Fu; Xinyi Peng; Yili Zhou; Junjie Xia; Ming Chen; Yang Li; Shengyuan Li; Min Shi; Xunli Xia; Bo Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Knowledge-guided graph machine learning for spatially distributed prediction of daily discharge and nitrogen export dynamics - Jie Yang; Bin Peng; Yaji Wang; Zewei Ma; Qianyu Zhao; Licheng Liu; Xiaowei Jia; Vipin Kumar; Ming Pan; Mengqi Jia; Xiang Li; John Nieber; et al. (Water Research, 2026)

A potent TGF-β heterodimer orchestrates germ cell homeostasis in fish - Ming-Tao Wang; Chun Miao; Sheng Yang; Zhi Li; Meng-Di Zhu; Jie He; Miao Ding; Si-Wei Wu; Yang Zhang; Shun Li; Meng Lu; Peng Yu; et al. (Science Bulletin, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Corrigendum to “Modification of starch traits in commercial wheat through TaWaxy gene editing” [Carbohydrate Polymers 368 (2025): 124105] - Yuliang Qiu; Xi Li; Ming Fan; Huali Tang; Shuangxi Zhang; Weihong Huang; Zhiyang Han; Surong Wang; Hao Peng; Yonggui Xiao; Xingguo Ye; Ke Wang (Carbohydrate Polymers, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Effects of parachute science on local research capacity 降落伞科学对当地研究能力的影响 - Li Yang; Tao Chen; Colin A. Chapman; Paul A. Garber; Yu Xuan Fan; Tien Ming Lee; Michael Huffman; Juan Carlos Serio Silva; Carlos Peres; Onja H. Razafindratsima; Lwin Ngwe; Peng Fei Fan (Conservation Biology, 2026)
Strengthening research capacity is essential to address the global biodiversity crisis. Yet, parachute science often undermines this goal, and its prevalence, costs, and benefits are unclear. We analyzed 13,502 publications on primate research that we extracted from Scopus (1960–2022) to evaluate the effects of parachute science on local research capacity across primate‐range countries. We categorized these publications as local (LRP), collaborative (CRP), or parachute science (PSRP) research publications and categorized countries where the research took place as low‐ to middle‐income countries or high‐ to upper‐middle‐income countries. We used generalized linear mixed‐effects models to assess how parachute science influenced local research capacity. For 69% of PSRPs, the research was conducted in 59 low‐ to middle‐income countries. For 20% of LRPs, research was led by people from these 59 countries. The disparity in LRPs among country groups was large. Local research publications in high‐ to upper‐middle‐income countries were at least 3.6 times higher than those in low‐ to middle‐income countries. Before 2013, parachute science contributed to an increase in LRPs; this trend reversed after 2013, mainly resulting in a decline in LRPs across all countries and both income categories. Strengthening the capacity to share research in low‐ to middle‐income countries is urgent if international conservation commitments are to be met. We recommend establishing true collaborative and interdisciplinary research teams, expanding local research opportunities, and supporting long‐term research projects as key strategies for sustainable research capacity strengthening in low‐income countries.

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Toward sustainable lithium recovery from brine: a hydrothermal carbon-coating strategy for minimizing Mn dissolution in ion-sieve adsorbents - Tianshu Bao; Congcong Li; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Lili Yu; Xinjuan Hou; Aiping Peng; Ming Ye (Resources, Conservation and Recycling, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Future impacts of climate change and land-use dynamics on streamflow and nutrient export in the Changbai Mountains of Northeast China under multi-scenario SWAT modeling - Jin Zhang; Yuhong Li; Wenguang Zhang; Peng Qi; Mingming Feng; Shuo Yan; Ming Jiang; Yuanchun Zou (CATENA, 2026)

Light-at-night exposure drives myopia via melanopsin signalling - Jiaxin Li; Congying Li; Meijun Wang; Jianjun Meng; Jiajia Dang; Ying Huang; Di Shi; Xinyu Li; Shan Cai; Tianli Peng; Yunfei Liu; Yuting Kang; et al. (Science China Life Sciences, 2026)

Effects of Different Attractants on Growth, Antioxidant Capacity, and Feeding Gene Expression of Procambarus clarkii - Youhai Du; Silei Xia; Wuxiao Zhang; Wenping Yang; Yebing Yu; Zhaoxia Li; Bin Peng; Yude Wang; Bo Liu; Hongyan Tian; Jianhua Ming (Fishes, 2026)
The purpose of this study was to investigate the effects of different feeding-promoting substances added to high plant protein diets on the growth, antioxidant, serum biochemical parameters, immune, and feeding-related genes of Procambarus clarkii. A total of 450 crayfish (3.94 ± 0.03 g) were selected and randomly divided into six groups, with each group consisting of three replicates and 25 crayfish per replicate. The crayfish were fed a basal diet without attractant (control group) and five experimental diets supplemented with 0.4% betaine (BET), 0.4% trimetlylamine oxide (TMAO), 0.4% squid paste (SQU), 0.4% dimethyl-β-propiothetin (DMPT), and 0.4% taurine (TAU). The feeding trial lasted for 6 weeks. The results showed that compared with the control group, the BET, SQU, DMPT, and TAU groups significantly improved in growth performance, weight gain rate, and specific growth rate of crayfish. Compared with the control group, the BET, MTAO, and SQU groups significantly increased hepatopancreas SOD, CAT, and T-AOC. Histological results showed that compared with the control group, all feeding attractant groups could alleviate hepatopancreas tissue damage. Compared with the control group, the TMAO and SQU groups significantly reduced serum GLU content as well as ACP and AKP activities. The results of gene quantitative analysis showed that, compared with the control, TMAO significantly upregulated the expression of tlr, nf-kb, propo, hsp70, and tgf-β, while TAU significantly increased the expression of hsp70, hsp90 and nf-kb genes. Compared with the control group, the expression levels of tor, 4ebp1, and s6k1 in the TMAO group were significantly increased. Compared with the control group, the expression levels of leptin and npy genes in the DMPT group were significantly increased. In summary, the addition of attractants to high plant protein feed has the effects of promoting growth, enhancing antioxidant capacity, improving digestive enzyme activity, alleviating hepatopancreas injury, improving immunity, and promoting feeding.

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Apoptosis and FoxO signaling axis form the core antiviral defense in mud crab (Scylla paramamosain) against MCRV - Xiaoyu Wang; Liangyu Chen; Jing Peng; Zixuan Luo; Ming Zhang; Qian Sun; Ngoc Tuan Tran; Xianliang Zhao; Yueling Zhang; Zhixun Guo; Shengkang Li (Aquaculture, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Dip-coated TiO2-SSM with polarity-regulated underliquid superlyophobicity for high-flux separation of immiscible liquids - Jing Zhang; Jiale Li; Kun Zhang; Yingyi Li; Yanting Zhang; Nan Jiang; Peng Chen; Ming Zhang; Meitong Li (Journal of Water Process Engineering, 2026)

Multidimensional evidence of the positive effects of land use on plant biodiversity in the Hengduan Mountains - Yu Huang; Peng Luo; Honglin Li; Hao Yang; Wenwen Xie; Chuan Luo; Honghong Jia; Yue Cheng; Ming Ni; Zhixiang Sun; Zhouyu Luo; Jiang He (Journal of Environmental Management, 2026)

The role of VxrB in Vibrio harveyi and evaluation of a VxrB knock-out as a vaccine candidate - Yinhui Peng; Xin Lu; Ming Liu; Shuo Hu; Lulu Liu; Renjie Li; LuJia Yang; Xiaohui Cai; Shuanghu Cai (Fish & Shellfish Immunology, 2026)

Achieving synergistic improvements in maize yield and nitrogen use sustainability through a novel high-density production system enabled by precision stage-specific regulation - Liang Fang; Dongping Shen; Zhen Wang; Linli Zhou; Tingting Zhang; Guoqiang Zhang; Jun Xue; Ruizhi Xie; Peng Hou; Keru Wang; Bo Ming; Ling Gou; et al. (European Journal of Agronomy, 2026)

CCUS technology diffusion and multi-agent investment behavior under policy incentives - Yuanming Li; Bei Li; Shuangxing Liu; Ming Xue; Xingchun Li; Peng Wu (Energy Policy, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

Ultrasensitive and label-free detection of piR-54265 biomarker by solution-gated graphene transistors with poly-adenine DNA assembled probe for accurate diagnosis of colorectal cancer - Tingting Yu; Peng Song; Ruixue Wang; Ziwen Chen; Liang Zhao; Ming Wang; Jianying Wang; Tao Mei; Xianbao Wang; Jinhua Li (Chemical Engineering Journal, 2026)

Beyond Labels: A Survey of Label-Efficient Deep Learning Techniques in Seismic Exploration - Ming Li; Peng Xu; Xuesong Yan; Chengyu Hu; Qinghua Wu; Mingliang Hu (Surveys in Geophysics, 2026)

Blast Fragmentation Prediction Model Based on Energy Fan Theory - Dongqiang Liu; Xinhua Zeng; Ming Chen; Peng Zhang; Jiangping Yan; Wenbo Lu; Fengze Zhao; Mingze Li; Zhanzhi Tan (Rock Mechanics and Rock Engineering, 2026)

Semi-analytic Solutions for Long-Term Stress–Strain Behavior of Rock Salt Using Fractional Burgers Model and Transformed Differential Quadrature Method - Yong Zhi Zhao; Junliang Li; Ming Peng; Yan Zhu; Zhenming Shi (Rock Mechanics and Rock Engineering, 2026)

Global Patterns and Drivers of Recent Decoupling Between Extratropical Spring Phenology and Temperature - Ziyu Lu; Ming Shao; Jiayan Li; Jingyuan Lin; Peiyuan Tao; Mengyu Li; Siqi Zhang; Peng Yao; Yang Fu (Global Change Biology, 2026)
While spring phenology has been widely studied, the magnitude and drivers of its decoupling from thermal cues across extratropical biomes remain poorly understood. Using satellite data from 1982 to 2021, we show that the onset of vegetation green‐up (GSOS) generally lags the onset of the thermal growing season (TSOS). This mismatch (ΔSOS) has increased by 1.51 days per decade ( p 15 days), warming‐driven advances in TSOS are increasingly decoupled from GSOS, as declining precipitation and enhanced evaporative demand intensify moisture limitation and delay green‐up; in temperate forests (both coniferous and broadleaf), warming together with enhanced shortwave radiation promotes faster GSOS advancement relative to TSOS, thereby dampening the mismatch. These contrasting pathways reveal an accelerating yet heterogeneous phenology–temperature decoupling, with far‐reaching consequences for ecosystem synchrony, seasonal carbon uptake, and land–climate feedbacks. Our results underscore the need to incorporate non‐thermal drivers and biome‐specific controls into phenological and Earth system models to better constrain future climate–biosphere interactions.

Source Control of the Seismic Energy Radiation in Rock Blasting - Yongzhen Li; Wenbo Lu; Yang Wang; Ming Chen; Peng Yan; Ting Meng; Jiawei Zheng (Rock Mechanics and Rock Engineering, 2026)

Numerical investigation on hydrodynamic characteristics of floating breakwater with wings using a coupled SPH method - Xin Chen; Ming-yuan Li; Peng-cheng Shi; Hong-lei Lyu; Jie Cui (Marine Georesources & Geotechnology, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Synergistic mechanism for greenhouse gases reduction, pollution control, and economic development in the plastic packaging industry: A coupled analysis of material, value, and environmental flows - Mingxuan Tuo; Ming Yang; Yifan Gu; Guangwen Hu; He Peng; Rui Li; Tong Liu; Yufeng Wu (Resources, Conservation and Recycling, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sustainable oil-water separation via recycled PE-modified waste cotton fibers: Fabrication, performance, and integrated automated system - Jiale Li; Jing Zhang; Shixuan Bo; Zhengkang Shi; Yutong Jiao; Yanting Zhang; Peng Chen; Ming Zhang; Meitong Li (Journal of Water Process Engineering, 2026)

A molecular understanding of the potent health of wholemeal sourdough bread derived from different lactic acid bacterial fermentation - Cheng Chen; Anqi Wang; Haotian Wu; Ming Ning; Peng Yu; Ning Li; Chris Blanchard; Zhongkai Zhou; Weining Huang (Journal of Cereal Science, 2026)

Effects of three freezing treatments on the quality of frozen chow mein noodles - Pengyuan Tian; Ping Jiang; Ming Liu; Naijuan Wang; Lijuan Zhang; Sijia Xu; Peng Yin; Weiqing Zhang; Mingfu Yu; Dan Li (Journal of Cereal Science, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Mechanistic insights into structural evolution of goji berry (Lycium barbarum L.) during pulsed vacuum drying procedure via moisture migration and cell wall polysaccharide transformations - An-An Zhang; Li-Zhen Deng; Long Xie; Ze-Kang Peng; Ming-Qiang Xu; Wan-Liang Hao; Yu-Hao Jiang; Wen-Bin Ze; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Activation of peroxymonosulfate by nickel-cobalt-based PBAs and their derivatives for tetracycline degradation: Degradation mechanism and toxicological evaluation - Wenting Sun; Shiyu Bian; Geng Li; Shuqi Peng; Yuwei Pan; Ming Zhang; Weinan Xing; Xin Huang; Guangyu Wu (Environmental Research, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

The yield-biomass-water-environment nexus model unravels the plastic mulching film dilemma: Yield gains vs. environmental cascades in China’s cotton systems - Yifan Gu; Zixin Bian; Qianqian Shi; Ziyi Zhao; Haixia Li; Rui Li; He Peng; Ming Yang; Qingbin Yuan; Yufeng Wu (Agricultural Systems, 2026)

Seismic Data Reconstruction and Noise Suppression Based on an Improved Weighted Fast Projection onto Convex Sets Algorithm - Gao-peng Cheng; Hua Zhang; Hong-xing Li; Yu Song; Ming Yue; Kai-dong Zhang (Applied Geophysics, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A novel strategy for improving canopy nitrogen density retrieval by deciphering saturation effects and vertical heterogeneity - Hongye Yang; Bo Ming; Chenwei Nie; Dayun Feng; Kexin Gao; Shang Gao; Jun Xue; Guoqiang Zhang; Peng Hou; Ruizhi Xie; Zhenhai Li; Xiuliang Jin; et al. (Computers and Electronics in Agriculture, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Palynological succession in Gzhelian No. 8 Thick Coal of the Taiyuan Formation, Ordos Basin, North China - Hui Zhang; Yun-He Shi; Peng-Shuai Jiao; Bo Pan; Feng Liu; Ming-Li Wan; Jing-Kun Zhang; Hui-Ping Peng (Palaeoworld, 2026)

Trace element geochemistry of magnetite and hematite from the Jinchang porphyry Au-Cu deposit, northeast China: Implications for fluid evolution and cobalt enrichment - Peng-Fei Shan; Ming-Jian Cao; Noreen J. Evans; Le Wang; Yi Li; Yu-Suo Zhao; Ke-Zhang Qin (Journal of Asian Earth Sciences, 2026)

Differential regulation of root iron plaque formation in a mangrove species, Kandelia obovata by biodegradable and conventional nanoplastics: Evidence from interfacial interactions, microbial communities, and redox conditions - Ming Li; Jie Gao; Nora Fung-Yee Tam; Haichao Zhou; Min Pan; Fred Wang-Fat Lee; Steven Jing-Liang Xu; Jian Liu; Kaixuan Deng; Peng Zheng; Cheng Ye; Xinran Ke; et al. (Environmental Pollution, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Preliminary design and analysis of a radar system model based-on a phased-array RF astro-receiver for space debris detection and tracking - Lalida Tantiparimongkol; Ming Shen; Peng-qi Gao; Xiao-zhong Guo; Huan-huan Yu; Jia-wei Li; Jia-lang Ding; Yu-ting Chu; Ran Duan; You Zhao (Advances in Space Research, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Semi-analytical characterization for the plastic development of deep-buried and water-rich non-circular tunnels considering out-of-plane stress based on three-dimensional strength criteria - Yu-ming Sheng; Dong Wang; Jin-feng Zou; Peng Li (Tunnelling and Underground Space Technology, 2026)

Advances in understanding the neurotoxicity of lead, cadmium, arsenic, and therapeutic strategies - Yi-Ling Li; Zhi-Xin Huang; Jian-chao Peng; Thanh-Tung Ho; Hai Huang; Michael Aschner; Yue-Ming Jiang (Toxicology Letters, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Complex terrain causes global model prediction biases of 21.7 Zhengzhou extreme precipitation - Peng Wei; Xin Xu; Ming Xue; Jian Li; Kun Zhao; Qinghong Zhang (Science Bulletin, 2026)

Calcium-phosphate mediated green remediation of uranium mine water: sulfur-fixing ash enhanced phosphorus leaching from phosphogypsum for targeted uranium mineralization - Xue Xia; Ming Guo; Dan Chen; Yinyin Peng; Jialin Li; E. Li; Chunyan Ma; Xiaoqin Nie; Faqin Dong (Journal of Water Process Engineering, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Secondary metabolites from the arial parts of Hyssopus cuspidatus Boriss. and their chemotaxonomic significance - Jian-Kang Lu; Gui-Juan Zheng; Jing-Jing Li; Xiao-Xia Jiang; Jin-Xin Zhan; Chang-Hao Yu; Xu Wang; Yi-Xuan Zeng; Tian-Jiao Qi; Hong Liu; Hui-Ming Peng; Jin-Bo Fang (Biochemical Systematics and Ecology, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

amh alleles on XY sex chromosomes regulate male differentiation in amphidiploid Carassius auratus - Chun Miao; Meng Lu; Miao Ding; Ming-Tao Wang; Zhi Li; Tian-Zi Yao; Zhi-Xuan Zhu; Wen-Xuan Du; Jun-Sheng Niu; Xiao-Juan Zhang; Shun Li; Peng Yu; et al. (Science China Life Sciences, 2026)

STAT6-Mediated SOCS2 Alleviates Cognitive Impairments and Neuronal Damage in Alzheimer’s Disease Rat Models and Aβ1-42-Stimulated HT-22 Cells - Yu Liu; Lang Peng; Ming Li; Wenjing Yan; Qingwei Xiang (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Research on decoupling and characterization methods of geological elements based on pre-stack seismic data - Cong Ren; Rong-rong Zhao; Ming-yi Li; Jing-jing Zong; Han-peng Cai; Wenhao Li (Applied Geophysics, 2025)

The Effects of Lead, Cadmium and Arsenic Exposure Alone or in Combination on Neurotoxicity Through Neural Signaling Pathways - Zhi-Xin Huang; Yi-Ling Li; Jian-Chao Peng; Thanh-Tung Ho; Hai Huang; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Automated TES analysis for polymer recycling via NeuroSymbolic AI - Yikang Li; Zhigang Wang; Ming Chen; Junyuan Cao; Nan Cai; Yanlong Peng; Yisheng Zhang; Hongshen Zhang (Process Safety and Environmental Protection, 2025)

Corrigendum to “An upscaling approach for estimating field-level irrigation water use through the Budyko framework” [J. Hydrol. 661 (2025) 133785] - Jingwen Zhang; Kaiyu Guan; Murugesu Sivapalan; Chongya Jiang; Ming Pan; Bin Peng; Wang Zhou; Trenton E. Franz; Xiaohong Chen; Kairong Lin; Zejun Li (Journal of Hydrology, 2025)

Optimizing molecular distillation film scraper by CFD and experiment: VE extraction from SODD - Mengyuan Zhou; Ziwei Yu; Qidong Xue; Peng Zhang; Zhengzhang Wu; Jie Mi; Kangning Li; Mingyang Yuan; Ruijie Liu; Ming Chang (Innovative Food Science & Emerging Technologies, 2025)

Experimental study on reinforcement and remediation of nickel-contaminated sludge using grouting vacuum preloading combined with electroosmosis - Peng Wang; Ming Li; Zhuoxuan Wu; Jun Wang; Guohui Yuan; Xianfeng Huang; Jianfeng Wu (Geotextiles and Geomembranes, 2025)

SensoryCharacterization ofChicken soup at different temperatures by using check-all-that-apply (CATA) analysis and temporal dominance of sensations (TDS) - Mingcheng Zhang; Luyi Jin; Peng Yu; Ming Li; Di Yu; Kaixian Zhu; Duoduo Zheng; Wensheng Yao; Dengyong Liu (Food Research International, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Biofilm with a mechanically strengthened character via enhanced cross-links of soybean proteins with short-chain fatty acid-modified starch - Sheng Ke; Gaoheng Li; Anqi Wang; Haotian Wu; Peng Yu; Ming Ning; Padraig Strappe; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2025)

Synergistic enhancement of waste activated sludge anaerobic digestion by iron-modified biochar activated peroxydisulfate: Dual mechanisms of pretreatment disintegration and bioelectrochemical enhancement - Zisheng Zhao; Peng Li; Xiaowei Wang; Tingting Zhang; Guangyi Zhang; Ming Dou (Chemical Engineering Journal, 2025)

A label-free magnetic enrichment SERS platform for ultra-sensitive detection and AI intelligent identification of novel coronavirus variants - Yusi Peng; Dan Li; Yanyan Li; Shuai Zhao; Meimei Xu; Weida Zhang; Zheng Teng; Ming Liu; Masaki Tanemura; Yong Yang (Chemical Engineering Journal, 2025)

An innovative intimately coupled photocatalysis and biodegradation system for simultaneous removal of emerging contaminants and nitrate - Shi-Ming Niu; Thangavel Sangeetha; Xue-Dong Zhang; Wei-Mon Yan; Peng-Fei Li; Jiří Ryšavý; Jakub Čespiva; Min-Hua Cui (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Lactylation-related multigene signature in multiple myeloma: integrated prognostic stratification, immune landscape profiling, and therapeutic guidance - Wuyang Zhang; Shuai Ming; Peng Cheng; Dan Shi; Jingyu Li; Bin Wang; Yu Fang; Mengru Li; Wei Cao; Min Wang; Zaibao Wang; Jiawei Xiao; et al. (Immunologic Research, 2025)

Multigenerational toxic effects of Butylparaben and Hexylparaben on Moina macrocopa - Xue Lei Hu; Ming Chen; Jin Lan Peng; He Ping Huang; Sui Jun Cai; Jin Ling Liu; Yun Hui Li; Lu Wang (Ecotoxicology, 2025)

Erratum to: Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Modified Xiaoyao San ameliorates LPS-induced depression-like behavior by inhibiting NLRP3-mediated microglial pyroptosis - Lei Tian; Pan Su; Gang Feng; Shuaijun Peng; Liming Liu; Xiangli Yan; Xianghua Liu; Yucheng Li; Ming Bai; Baoying Wang; Erping Xu (Metabolic Brain Disease, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Adaptive sliding mode control for underactuated ship-mounted cranes with dead zones and actuated/unactuated state constraints - Xin Zhang; Zengcheng Zhou; Yihao Shi; Ming Li; Wei Peng; Chen Song; Zhi Li; Xingong Cheng; Menghua Zhang (Ocean Engineering, 2025)

An upscaling approach for estimating field-level irrigation water use through the Budyko framework - Jingwen Zhang; Kaiyu Guan; Murugesu Sivapalan; Chongya Jiang; Ming Pan; Bin Peng; Wang Zhou; Trenton E. Franz; Xiaohong Chen; Kairong Lin; Zejun Li (Journal of Hydrology, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Genesis of the Pulang polymetallic mineralization system in Yunnan Province, China: Insights from in situ trace element and S isotope analyses of pyrite - Xiao-Yu Zhao; Zi-Chao Tang; Ming-Guo Deng; Wen-Chang Li; Jing-Wei Xu; Yan Su; Zhi-Peng Li; Lei Wang (Journal of Geochemical Exploration, 2025)

Orthogonal functional group tagging combined with computational retention time prediction for discovering furan fatty acids in plant oils - Hua-Ming Xiao; Xiao-Hui Peng; Shuai Zhao; Dilshad Hussain; Qin-Feng Zhang; Jian-Li Chen; Dan Luo; Fang Wei; Xian Wang (Food Chemistry, 2025)

Positively correlated singlet and triplet hybridization governed by excited-state energy alignment in organic photovoltaics - Yue Ren; Li-Yuan Peng; Hou Tong; Ming-Yang Li; Xue Wu; Guang-Yan Sun (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Modification of starch traits in commercial wheat through TaWaxy gene editing - Yuliang Qiu; Xi Li; Ming Fan; Huali Tang; Shuangxi Zhang; Weihong Huang; Zhiyang Han; Surong Wang; Hao Peng; Yonggui Xiao; Xingguo Ye; Ke Wang (Carbohydrate Polymers, 2025)

External and internal controls on decadal precipitation variability over North America - Xiaolu Fan; Jianping Huang; Yongkun Xie; Wenmin Wei; Yu Ren; Yihui Xu; Ming Peng; Li Fu (Climate Dynamics, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

Distribution, partitioning behaviors, and source identification of legacy and emerging per- and polyfluorinated alkyl substances in the Pearl River Estuary, South China - Bin Tang; Can Peng; Dong-Jing Zhou; Kai-Yi Wu; Fei Tian; Hai-Gang Chen; Shi-Yi Zhang; Bo-Wen Li; Guo-Cheng Hu; Ming-Zhong Ren; Jing Zheng (Water Research, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

A possible biotic precursor, Archaeodunaliella junggarensis n. gen. n. sp., in the Upper Paleozoic Fengcheng Formation from Junggar Basin, Northwest China - Li-Ye Zhu; Hua Zhang; Tian-Ming Shi; Peng Tang (Palaeoworld, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Morphology engineering-driven high-performance potassium-based CO2 adsorbents: Interface design and structure-activity relationship study - WeiMing Wang; YuHang Yu; Bo Li; Jun Xiong; GuoQiang Wei; XiXian Yang; Bo Deng; Ming Li; Shuai Peng; Hao Liu (Journal of Environmental Chemical Engineering, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Soil organic and inorganic carbon pools in the Loess Plateau: New estimation, change and trade-offs - Jianzhao Wu; Lei Deng; Yakov Kuzyakov; Yuanyuan Huang; Xiaodong Song; Ming Nie; Jianming Deng; Peng Zhao; Yang Liao; Lingbo Dong; Xiaozhen Wang; Jiwei Li; et al. (Global and Planetary Change, 2025)

Study on mechanism of in-situ hydrogen generation based on molecular dynamics simulation from pyrolysis of heavy oil - Houfeng He; Yuning Gong; Mingguo Peng; Haoran Zheng; Tian Feng; Ming Zhang; Qiu Li; Pengcheng Liu (Fuel, 2025)

Unraveling the applicability and thermal performance of PCM-impregnated wood in personalized comfort systems: Thermal manikin verification - Xiujie Li; Cheuk Ming Mak; Peng Xue; Rong Xue; Hai Ming Wong (Energy and Buildings, 2025)

Selectively passivated core-satellite cobalt-iron bimetallic phosphide with optimized ⁎OH adsorption for boosting oxygen evolution reaction - Baoshan Liu; Wangshu Zheng; Zhaoxi Zhang; Jiarui Yang; Yanqi Yuan; Feng Li; Jing Liu; Liping Zhao; Ming Wen; Han Chen; Peng Zhang; Lian Gao (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Potential tuning of polycrystalline piezoelectric component for effective energy-band structure and markedly enhanced H2 yield of photocatalytic component - Xinxin Jin; Yingshuang Zhang; Xiao Li; Peng Liu; Qinghao Ge; Zhihao Zhao; Xingzhang Li; Lige Gong; Zhiping Zhang; Dan Li; Feng-Ming Zhang; Limin Dong; et al. (Chemical Engineering Journal, 2025)

Impact of heat pre-treatment on microbial succession and antibiotic resistance gene spread in high-solid anaerobic digestion of pig manure - Jianlin Wang; Ming Wang; Minghan Xu; Yunting Li; Hao Peng; Kai Liu; Qingjie Wang (Chemical Engineering Journal, 2025)

Complexation-driven 3D printable whey protein-lotus root composite gels for dysphagia foods - Jinfeng Wang; Xueyu Jiang; Houze Gan; Siyu Li; Kaidi Peng; Ying Sun; Ming Ma; Yang Yi (Carbohydrate Polymers, 2025)

Neural Responses to Hypoxic Injury in a Vascularized Cerebral Organoid Model - Yang Li; Xin-Yao Sun; Peng-Ming Zeng; Zhen-Ge Luo (Neuroscience Bulletin, 2025)
Hypoxic injury (HI) in the prenatal period often causes neonatal neurological disabilities. Due to the difficulty in obtaining clinical samples, the molecular and cellular mechanisms remain unclear. Here we use vascularized cerebral organoids to investigate the hypoxic injury phenotype and explore the intercellular interactions between vascular and neural tissues under hypoxic conditions. Our results indicate that fused vascularized cerebral organoids exhibit broader hypoxic responses and larger decreases in panels of neural development-related genes when exposed to low oxygen levels compared to single cerebral organoids. Interestingly, vessels also exhibit neural protective effects on T-box brain protein 2 + intermediate progenitors (IPs), which are markedly lost in HI cerebral organoids. Furthermore, we identify the role of bone morphogenic protein signaling in protecting IPs. Thus, this study has established an in vitro organoid system that can be used to study the contribution of vessels to brain injury under hypoxic conditions and provides a strategy for the identification of intervention targets.

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Genome-wide association and genomic selection studies on feed efficiency with fishmeal-free feed in large yellow croaker (Larimichthys crocea) - Gongsi Wang; Yingbo Yuan; Xiaotong Li; Ranxin Fu; Xingcheng Zhu; Zhenye Zhao; Yuhan Jin; Sen Zhang; Peng Ren; Lining Zhang; Qinghui Ai; Ming Fang; et al. (Aquaculture, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Highly flexible and multifunctional lyocell-basalt fiber filter media for high-performance air filtration - Ze-Xin Chen; Desalegn Atalie; Hui Li; Ming-Cheng Gao; Peng-Cheng Ma (Journal of Hazardous Materials, 2025)

Long-term early warning threshold estimation of landslide deformation in reservoir area through multi-objective optimization inversion - Yi Li; Erfeng Zhao; Chenfei Shao; Yanxin Xu; Haifeng Huang; Peng Ge; Ming Chen (Engineering Geology, 2025)

Biomimetic Ti3C2 nanosheets for synergistically overcoming chemoresistance and boosting immunotherapy via enhanced cuproptosis in cancer - Shuaiyin Zhang; Xinran Xie; Ming Liu; Zhixin Li; Yang Ye; Liang Peng; Kexing Lyu; Xiaomei Sun; Yuan Yuan; Zhijun Zhang; Weiping Wen; Zhaoxu Tu (Chemical Engineering Journal, 2025)

Electrophysiological Signatures of Visual Sensations Elicited by Direct Electrical Stimulation - Yan-Yan Li; Bo Zhang; Jing Wang; Yuri B. Saalmann; Mohsen Afrasiabi; Peng-Cheng Lv; Hai-Xiang Wang; Huan-Huan Xiang; Meng-Yang Wang; Guo-Ming Luan; Robert T. Knight; Liang Wang (Neuroscience Bulletin, 2025)

Wave parameter analysis of landslide-tsunamis - Ming Peng; Qingxin Zhao; Yan Zhu; Shuang Li; Hongchao Zheng; Shaoqiang Meng (Natural Hazards, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Risk of sustainable agricultural water supply and security strategy in the Black Soil Region of Northeast China - Peng Qi; Haiqing Wang; Yingbin Wang; Xiaoyu Li; Shirong Liu; Shougong Zhang; Ming Jiang; Guangxin Zhang (Science Bulletin, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Corrigendum to “Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations” [Comput. Geotech. 182 (2025) 107160] - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

A hybrid surrogate-assisted dual-population co-evolutionary algorithm for multi-area integrated scheduling in wafer fabs - Mengyu Jin; Peng Zhang; Youlong Lv; Ming Wang; Wenbing Xiang; Hongsen Li; Jie Zhang (Swarm and Evolutionary Computation, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Numerical prediction of premixed syngas/air explosion in a closed duct using a reduced combustion mechanism - Kai Zheng; Zhifeng Zhou; Qianhang Jia; Ming Peng; Song Lin; Yuyang Li (Fuel, 2025)

In-situ combination of CeO2-Au/SnO2 with g-C3N4 nanotubes as superior tubular catalysts for synergistically boosting the nitroaromatic reduction - Jiasheng Fang; Ming Chen; Xusheng Wang; Zhenting Huang; Shuo Zhao; Peng Wang; Qing Li; Guangfu Liao (Chemical Engineering Journal, 2025)

Spatial and temporal characteristics of vegetation resilience to drought in China - Mengyuan Wei; Liang Jiao; Peng Zhang; Ruhong Xue; Xuge Wang; Qian Li; Ming Jin (Science China Earth Sciences, 2025)

Pilot Exploration of RGMa-BMP4 Signaling in Neutrophil Activation in NMOSD: Integrating Clinical and Molecular Insights - Weihe Zhang; Lei Cui; Yeqiong Zhang; Yang He; Xiaoxuan Li; Yu Wang; Jinsong Jiao; Dantao Peng; Ming Jin; Cheng Xiao (Molecular Neurobiology, 2025)

Chronic and Intergenerational Toxicity of Chloramine-T in Moina macrocopa Following Prolonged Exposure - Xue Lei Hu; Sui Jun Cai; Ming Chen; Le Yi Lin; Jin Lan Peng; Jin Ling Liu; Yun Hui Li; Lu Wang (Bulletin of Environmental Contamination and Toxicology, 2025)

Numerical simulation of the effect of solar chimneys on NOx-O3 photochemical reaction and ventilation in urban street canyon - Hanbing Xiong; Tianhao Shi; Yongjia Wu; Ruiyue Xia; Xitong Yuan; Renaud de Richter; Wei Li; Yueping Fang; Nan Zhou; Wenyu Li; Chong Peng; Tingzhen Ming (Urban Climate, 2025)

Hydrological connectivity creates additional cooling effects for urban wetland complexes - Wenwen Xie; Hao Yang; Peng Luo; Honglin Li; Shijun Zhang; Yu Huang; Yue Cheng; Ming Ni; Sujuan Wu; Haoyu Yang (Urban Climate, 2025)

High-resolution sedimentary cyclostratigraphy and astronomical signals in the Upper Ordovician of Southwest China - Kai Wang; Ming-Song Li; Peng Tang; Jun-Xuan Fan; Ren-Bin Zhan; Jian-Bo Liu (Palaeoworld, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Efficient capture and detoxification of gaseous arsenic trioxide from flue gas using silicomanganese alloy dust - Xin-Peng Ma; Guang Yang; Guan-Ming Qiao; Song-Yao Liu; Jiao-Jiao Xie; Yuan-Peng Li; Chun-Gang Yuan (Journal of Environmental Management, 2025)

Nitrogen reduction and split application increased grain yield and agronomic nitrogen use efficiency of oilseed flax (Linum usitatissimum. L) by increasing nitrogen status - Ming Wen; Yuhong Gao; Lizhuo Guo; Bin Yan; Peina Lu; Bin Wu; Yifan Wang; Yue Li; Zhengjun Cui; Peng Xu; Haidi Wang; Yuanyuan Cui; et al. (Field Crops Research, 2025)

Significant effects of earthworm species on antibiotic resistome in livestock manure as revealed by metagenomic analysis - Ming Yang; Liang Peng; Meirui Mu; Fengxia Yang; Zhonghan Li; Bingjun Han; Keqiang Zhang (Environmental Pollution, 2025)

Design, synthesis, and application of negative ion-ion sieve synergistic adsorbent based on cross-linked carrier - Tianshu Bao; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Yong Wang; Xinjuan Hou; Aiping Peng; Ming Ye (Desalination, 2025)

Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Gold mineralization in the hydrothermal field at the termination of a detachment fault: A case study of the Tianxiu Vent Field - Ming Yang; Yejian Wang; Sven Petersen; Zhongyan Qiu; Honglin Li; Peng Zhou; Yiyang Cai; Xing Yu; Matthias Frische; Jiqiang Liu; Xiqiu Han (Mineralium Deposita, 2025)

Finite element modeling of clavicle fracture fixations: a systematic scoping review - Yi Zheng; Jing Li; Andy Yiu-Chau Tam; Timothy Tin-Yan Lee; Yinghu Peng; James Chung-Wai Cheung; Duo Wai-Chi Wong; Ming Ni (Medical & Biological Engineering & Computing, 2025)
Finite element analysis has become indispensable for biomechanical research on clavicle fractures. This review summarized evidence regarding configurations and applications of finite element analysis in clavicle fracture fixation. Seventeen articles involving 22 clavicles were synthesized from CINAHL, Embase, IEEE Xplore, PubMed, Scopus, and Web of Science databases. Most studies investigated midshaft transverse closed fractures by reconstructing intact models from CT scans and simulating fractures through gap creation. Common loading schemes included axial compression, distal torsion, and inferior bending. The primary objective was comparing different implant designs/placements on construct stiffness, von Mises stress, and fracture site micro-motion. Our review suggested a preference for plate fixation, particularly with anterior placement, for midshaft transverse fractures. However, limited fracture types studied constrain comprehensive recommendations. Additionally, the review highlighted discrepancies between finite element and clinical studies, emphasizing the need for improved modeling of physiological conditions. Future research should focus on developing a comprehensive database of finite element models to test various implant options and placements under common loading schemes, bridging the gap between biomechanical simulations and clinical outcomes. Graphical Abstract

Hydrogen peroxide regulated split-type electrochemiluminescence sensing platform for non-invasive detection of gastric cancer-associated D-amino acids - Juan Li; Ming-Chun Lai; Ya-Meng Zhong; Ya-Ling Chen; Na Wu; Wei Chen; Hua-Ping Peng (Analytica Chimica Acta, 2025)

YOLO-DAFS: A Composite-Enhanced Underwater Object Detection Algorithm - Shengfu Luo; Chao Dong; Guixin Dong; Rongmin Chen; Bing Zheng; Ming Xiang; Peng Zhang; Zhanwei Li (Journal of Marine Science and Engineering, 2025)
In computer vision applications, the primary task of object detection is to answer the following question: “What object is present and where is it located?”. However, underwater environments introduce challenges, such as poor lighting, high complexity, and diverse marine organism shapes, leading to missed detections or false positives in deep learning-based algorithms. To improve detection accuracy and robustness, this paper proposes an enhanced YOLOv11-based algorithm for underwater object detection that strengthens the ability to capture both local and global details and global contextual information in complex underwater environments. To better capture local and global features while integrating contextual information, the proposed method introduces several enhancements. The backbone incorporates a DualBottleneck module to enhance feature extraction, replacing the standard bottleneck structure in C3k, thus enhancing the feature extraction and the channel aggregation. The detection head adopts DyHead-GDC, integrating ghost depthwise separable convolution with DyHead for greater efficiency. Furthermore, the ADown module replaces conventional feature extraction and downsampling convolutions, reducing parameters and FLOPs by 14%. The C2PSF module, combining focal modulation and C2, strengthens local feature extraction and global context processing. Additionally, a SCSA module is inserted before the detection head to fully utilize multi-semantic information, improving the detection performance in complex underwater scenes. Experimental results confirm the effectiveness of these improvements. The model achieves 84.2% mAP50 on UTDAC2020, 84.4% on DUO and 86.7% on RUOD, surpassing the baseline by 2.5%, 1.6% and 1.2%, respectively. It remains lightweight, with 6.5 M parameters and a computational cost of 7.1 GFLOPs.

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

Temperature-tuned dual-selective NO2/diisopropylamine sensor based on (NH4)0.33WO3 doped γ-WO3 nanosheets-assembled hollow microspheres via simple pyrolysis of commercial ammonium metatungstate - Guo-Li Chen; Hui-Ye Jiang; Yan Jiang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Geomorphic and geologic controls on large-scale landslides in the Himalayan region of China - Yu-Feng Wang; Peng-Hai Chen; Jia-Zhen Qian; Qian-Gong Cheng; Jie Ming; Chuan-bao Li (Landslides, 2025)

Optimal nitrogen distribution in maize canopy can synergistically improve maize yield and nitrogen utilization efficiency while reduce environmental risks - Xiaoxia Guo; Wanmao Liu; Yunshan Yang; Guangzhou Liu; Bo Ming; Ruizhi Xie; Keru Wang; Shaokun Li; Peng Hou (Agriculture, Ecosystems & Environment, 2025)

Effects of Subchronic Manganese and Iron Exposure, Alone or in Combination, on Elemental Distribution in Rats - Yan Li; Jian-chao Peng; Yuan-yuan Fang; Li-mei Qin; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2025)

Effect of Sodium Para-Aminosalicylic Acid on Cuproptosis in PC12 Cells Exposed Manganese, Iron, and Copper - Hai Huang; Thanh-Tung Ho; Zhi-Xin Huang; Yi-Ling Li; Jian-Chao Peng; Viet-Phuong-Nguyen Nguyen; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Tumor cell-derived N-acetyl-aspartyl-glutamate reshapes the tumor microenvironment to facilitate breast cancer metastasis - Jie Xia; Lixing Zhang; Wucheng Zhu; Juchuanli Tu; Xilei Peng; Qiaodan Deng; Siqin Li; Xueyan He; Haonan Dong; Cuicui Liu; Xian Chen; Jiahui Xu; et al. (Science Bulletin, 2025)

Jatrophane and ingenane diterpenoids with anti-inflammatory activity from Euphorbia esula - Yu-Peng Li; Ying Li; Wen-Jing Gao; Chu-Hong Fang; Ming-Jun Lv; Jian-Min Yue; Jin-Hai Yu (Phytochemistry, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Impact of living environment on sleep quality in older adults and the mediating role of depression: a cross-sectional study - Jiayi Sun; Ming Yang; Sicheng Liu; Xiange Zhang; Wangquan Xu; Juanjuan Peng; Yueli Song; Li Wang; Guixia Fang (Sleep and Biological Rhythms, 2025)

Overview of the Mineralosphere and research progress on its environmental effects - Mengxi Feng; Ming Zhang; Peng Cai; Xinnan Li; Yongguan Zhu; Keqing Xiao (Science China Earth Sciences, 2025)

Uncertainty characterization, propagation, and evaluation in debris flow run-out hazard assessment - Peng Zeng; Junlong Chen; Ming Chang; Xiaoping Sun; Tianbin Li (Landslides, 2025)

Source Characteristics and Induced Hazards of the 2025 M6.8 Dingri Earthquake, Xizang, China, Revealed by Imaging Geodesy - Chen Yu; Zhenhong Li; Xiaoning Hu; Chuang Song; Suju Li; Haihui Liu; Jie Li; Bingquan Han; Zhenjiang Liu; Ming Liu; Shuang Zhu; Xiaoye Hao; et al. (Journal of Earth Science, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Automatic extraction and quantitative analysis of characteristics from complex fractures on rock surfaces via deep learning - Mingze Li; Ming Chen; Wenbo Lu; Peng Yan; Zhanzhi Tan (International Journal of Rock Mechanics and Mining Sciences, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Microbial mechanism for improving biogas production performance from boiling acidified pig manure feedstock - Ming Wang; Kai Liu; Qichen Li; Yunting Li; Hao Peng; Qingjie Wang; Manman Wang; Wenzhe Li (Bioresource Technology, 2025)

Fully hydro-mechanical coupled analyses of the deep excavation above a multi-aquifer-aquitard system - Ming-Guang Li; Yue-Heng Yan; Zhong-Hua Xu; Hao-Biao Chen; Chen-Xin Peng; Jin-Jian Chen (Tunnelling and Underground Space Technology, 2025)

Metabolomics based early warning model for acute kidney injury risk in patients exposed to diquat - Shengkai Zhu; Xinyu Li; Chengzhao Wu; Xu Zhao; Shuiying Xu; Yujing Zhao; Xiaobo Peng; Xiaohe Xiao; Ming Niu (Toxicology and Applied Pharmacology, 2025)

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Gentidelasides A−G: Loganin derivatives from Gentiana delavayi with reducing Aβ secretion via suppressing BACE1 expression - Hai-Hui Guo; Chun-Xu Li; Min Yang; Feng-Feng Li; Hui-Yun Yang; Ming Yin; Jia-Peng Wang; Fu-Sheng Wang (Phytochemistry, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Regional disparities in PPCPs contamination of urban wastewater treatment plants: Unveiling influential factors and ecological effects - Xing Chen; Xiaofei Lu; Jiahua Peng; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Ming Hu; Bin Shi (Environmental Pollution, 2025)

Residential power scheduling based on consumption efficiency considering users’ utility sacrifice in smart grid - Xunyan Jiang; Lei Wu; Li Yan; Renhua Huang; Jia Peng; Ming Tang (Energy and Buildings, 2025)

Recent progress in flexible materials for wearable devices for body function and athletic performance monitoring - Ming Yang; Kelin Peng; Zhen Li; Yanan Gao; Qingquan Tian; Zhixiong Zhou; Yu Chen (Chemical Engineering Journal, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Impacts of Physical Parameterization Schemes on Typhoon Doksuri (2023) Forecasting from the Perspective of Wind–Wave Coupling - Lihua Li; Bo Peng; Weiwen Wang; Ming Chang; Xuemei Wang (Journal of Marine Science and Engineering, 2025)
Tropical cyclones (TCs) form over warm ocean surfaces and are driven by complex air–sea interactions, posing significant challenges to their forecasting. Accurate parameterization of physical processes is crucial for enhancing the precision of TC predictions. In this study, we employed the Weather Research and Forecasting model coupled with the Simulating Waves Nearshore (WRF-SWAN) model to forecast Typhoon Doksuri (2023), which exhibited a secondary intensification process in the South China Sea (SCS). We also investigated its sensitivity to various atmospheric physical parameterization schemes (PPS). The findings indicate that improvements in microphysical and cumulus convection parameterizations have significantly enhanced the prediction accuracy of Typhoon Doksuri’s trajectory and intensity. The simulation of sea surface heat flux is primarily influenced by the microphysical scheme, while the cumulus convection scheme substantially affects the representation of the typhoon core’s size and shape. Variations in the wind field induce differences in wave height, potentially reaching up to 2–3 m at any given moment. This study provides valuable insights into the effective selection of physical parameterizations for improving typhoon forecasts.

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

Dynamics of high-yielding maize genotypes under intensive management across multiple environments - Rongfa Li; Guoqiang Zhang; Ruizhi Xie; Peng Hou; Bo Ming; Jun Xue; Keru Wang; Shaokun Li (European Journal of Agronomy, 2025)

An insight into the effect of gas on pore clogging using a resolved CFD-DEM coupling model - Tuo Wang; Zhenming Shi; Ming Peng; Mengli Li (Computers and Geotechnics, 2025)

RDT-FragNet: A DCN-Transformer network for intelligent rock fragment recognition and particle size distribution acquisition - Mingze Li; Ming Chen; Wenbo Lu; Fengze Zhao; Peng Yan; Jie Liu (Computers and Geotechnics, 2025)

Multi-modal resonance of topological hybrid graphene foam for enhanced acoustic absorption - Chengqi Zhang; Wenhao Tong; Huasong Qin; Xin Ming; Lidan Wang; Yue Yu; Yi Mao; Jiahao Lu; Peng Li; Tongyang Shi; Kai Pang; Yingjun Liu; et al. (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

Huanglian decoction prevents and treats radiation-induced intestinal injury in lung cancer by regulating endoplasmic reticulum stress - Liang-liang Shi; Ya-ping Chen; Hao-ming Guo; Xue-peng Wang; Yang-yang Li; Shuai-zhe Wang; Shang-zu Zhang; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Journal of Natural Medicines, 2025)

Community Assembly Mechanisms of nirK- and nirS-type Denitrifying Bacteria in Sediments of Eutrophic Lake Taihu, China - Mamun Abdullah Al; Dandan Zhang; Sirui Liu; Yuzhen Ming; Mingyue Li; Peng Xing; Xiaoli Yu; Mingyang Niu; Kun Wu; Wei Xie; Zhili He; Qingyun Yan (Current Microbiology, 2025)

Participatory actions for investigating eco-craft trail activities: a case of Pinglin in Taiwan - Ming-Feng Huang; Li-Pei Peng (Paddy and Water Environment, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Dietary Iodine Can Effectively Alleviate the Adverse Effects of Fermented Rapeseed Meal on the Growth, Liver Health, and Antioxidant Capacity of Tilapia (GIFT, Oreochromis niloticus) - Di Peng; Ya-Xue Li; Li-Xue Dong; Ke Cheng; Hua Wen; Juan Tian; Jian-Min Zhang; Yang-Yang Liu; Wei-Hua Gao; Yong Min; Ming-Dian Liu; Ming Jiang (Fishes, 2024)
An 8-week feeding trial was conducted to evaluate the effects of dietary fermented rapeseed meal (FRM), potassium iodide, and their interactions on growth performance, approximate composition, and antioxidant capacity in tilapia, Oreochromis niloticus (initial body weight: 3.50 ± 0.15 g). Six isonitrogenous and isolipidic diets from a 2 × 3 factorial design were formulated with two levels of FRM (25.8 and 51.6%) and three levels of potassium iodide (0, 6, and 12 mg/kg), respectively. The results indicated that dietary levels of FRM and iodine had no significant influence on the SR of tilapia but exerted significant effects on weight gain (WG), specific growth rate (SGR), feed intake (FI), hepatosomatic index, and viscerosomatic index. The WG, SGR, and FI of tilapia in the 51.6% FRM groups were significantly lower than those in other groups (p

Polystyrene microplastics alleviate the developmental toxicity of silver nanoparticles in embryo-larval zebrafish (Danio rerio) at the transcriptomic level - Qiao-hong Xiao; Hao Xiang; Ya-nan Tian; Jiao-long Huang; Ming-qun Li; Pu-qing Wang; Kai Lian; Peng-xia Yu; Meng-yao Xu; Ruo-nan Zhang; Yan Zhang; Jie Huang; et al. (Science of The Total Environment, 2024)

Hydrogen sulfide alleviates cadmium stress in germinating carrot seeds by promoting the accumulation of proline - Miao Sun; Huan-Xuan Qiao; Tao Yang; Peng Zhao; Jun-Hao Zhao; Jia-Ming Luo; Hai-Ye Luan; Xiang Li; Sheng-Cai Wu; Ai-Sheng Xiong (Journal of Plant Physiology, 2024)

Nitrogen dynamic transport processes shaped by watershed hydrological functional connectivity - Ming Lei; Yu Long; Taoxi Li; Yichun Ma; Guangjie Zhang; Bo Peng; Zhongwu Li; Yaojun Liu (Journal of Hydrology, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Characterization of core microbiota of barley seeds from different continents for origin tracing and quarantine pathogen assessment - Xin Zhou; Fang Liu; Chun-Chun Wang; Hui-Li Zhang; Peng Zhao; Fu-Hong Xie; Dian-Ming Hu; Wei-Jun Duan; Lei Cai (Food Microbiology, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Polyoxometalate oxate solution: An electrolyte additive to sustainably improve the anodes electrode of aqueous Zn ion batteries - Li-li Du; Zhuo Li; Wei-jia Song; Qing-peng Bao; Peng-fei Wang; Zhe Gong; Yu-hang Zhang; Yu-han Wu; Fa-nian Shi; Ming-dong Zhou; Kai Zhu (Chemical Engineering Journal, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Disintegration of Cav-1/β-catenin complex attenuates neuronal death after ischemia–reperfusion injury by promoting β-catenin nuclear translocation - Peng Guo; Wan Wang; Zhiyan Liang; Yihang Li; Xiangling Ou; Ming Li; Bin Wang; Xuewen Wei; Linyan Huang; Suhua Qi (Molecular Biology Reports, 2024)

Mechanism underlying the rapid growth of Phalaenopsis equestris induced by 60Co-γ-ray irradiation - Yang Meng; Wei Li; Yunxiao Guan; Zihan Song; Guoren He; Donghui Peng; Feng Ming (Molecular Genetics and Genomics, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

The Comparison between Pilot-Grade Spray Dryer and Laboratory-Grade Spray Dryer: Structure, Powder Properties and Application for Direct Compaction - Zhe Li; Wanghai Peng; Fucai Chen; Lin Zhu; Abid Naeem; Weifeng Zhu; Yongmei Guan; Yi Feng; Yanni Wu; Xiao Lin; Liangshan Ming (AAPS PharmSciTech, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Photobiomodulation ameliorates ovarian aging by alleviating oxidative stress and inflammation damage and improving mitochondrial function - Yu He; Rongan Ye; Yinbo Peng; Qing Pei; Lei Wu; Caixia Wang; Wei Ni; Ming Li; Yiqiu Zhang; Min Yao (Journal of Photochemistry and Photobiology B: Biology, 2024)

Fast concrete crack depth detection using low frequency ultrasound array SH waves data - Jian Shen; Liu Liu; Zhenming Shi; Shaojun Li; Ming Peng; Yao Wang; Chunsheng Liu (Journal of Applied Geophysics, 2024)

A newly identified secretory phospholipase A2 group XIIA homolog (LcPLA2XIIA) in Larimichthys crocea exhibits antimicrobial and antitumor activities - Shouhu Li; Chuang Qin; Shi-Ming Peng; Ya-Bing Wang; Yuan Wang; Xiao-Shan Wang; Jian-Gao Shi; Xin-Cang Li (Fish & Shellfish Immunology, 2024)

Planting halophytes increases the rhizosphere ecosystem multifunctionality via reducing soil salinity - Jin-Peng Hu; Yuan-Yuan He; Jian-Hong Li; Zhao-Long Lü; Yue-Wei Zhang; Yuan-Hong Li; Jia-Lü Li; Ming-Xu Zhang; Yan-Hua Cao; Jin-Lin Zhang (Environmental Research, 2024)

A 3D SPH framework for simulating landslide dam breaches by coupling erosion and side slope failure - Shuang Li; Ming Peng; Liang Gao; Chengzhi Xia; Yan Zhu (Computers and Geotechnics, 2024)

Controlled synthesis of CoFe@TiN composites and their rapid and efficient degradation of emerging organic pollutants: RhB as an example - Qi Jiang; Kunyue Luo; Kang Peng; Ling Li; Hongda Liu; Ming Chen; Min Cheng (Colloids and Surfaces C: Environmental Aspects, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

A multifunctional biomass-based solar interface evaporator with feather-like structure for efficient selective transport, antibacterial properties, salt resistance, and oil-fouling prevention - Peng Zhang; Xudan Liu; Ming Teng; Liuying Li; Xiaomeng Zhang; Wenjing Wang; Wenqing Wang; Xuechuan Wang; Xiaomin Luo (Chemical Engineering Journal, 2024)

A cyclic shift-temperature operation method to train microbial communities of mesophilic anaerobic digestion - Ming Wang; Yunting Li; Hao Peng; Kai Liu; Xiangjing Wang; Wensheng Xiang (Bioresource Technology, 2024)

ALKBH5 facilitates the progression of infantile hemangioma by increasing FOXF1 expression in a m6A-YTHDF2 dependent manner to activate HK-2 signaling - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2024)

A fire risk pre-warning framework for high-rise buildings based on unascertained method - Li-Ning Zhang; Xiang-Ming Wang; Jing An; Hong Xian Li; Jiao-Qian Guo; Guo-bo Han; Peng-Fei Gou (Environmental Science and Pollution Research, 2024)
The growing global interest in preventing and controlling fires in high-rise buildings reflects the increasing significance of this issue today. This research aims to establish an early warning framework for fire risk in high-rise buildings. Firstly, considering the importance of a scientific indicator system for the application of the model, this study combines the event analysis method with the building design fire code to identify 11 key risk factors that have a far-reaching impact on the prevention of fires in high-rise buildings. Based on identifying the risk factors, a high-rise building fire risk warning tree is also established, which scientifically solves the problem of the indicator system of the warning object. Subsequently, in response to the various complex issues arising from the uncertainty of fire occurrence in high-rise buildings, this study adopts the unascertained method to model the fire risk of high-rise buildings for early warning. In addition, the developed methodology was empirically validated through case studies and analyses of empirical data on fire risks in nine representative high-rise buildings. The results of the unascertained method were also compared with the results of the K-means method, from which it was concluded that the unascertained method can predict building fires more accurately. The research results provide a reliable decision support system for fire disaster prevention and control in high-rise buildings.

Ecosystem risk-based prioritization of micropollutants in wastewater treatment plant effluents across China - Jianchao Liu; Tian Ouyang; Guanghua Lu; Ming Li; Yiping Li; Jun Hou; Chao He; Peng Gao (Water Research, 2024)

Sesquiterpene lactones from Tithonia diversifolia with ferroptosis-inducing activities - Ao-Xue Ding; Yi-Ming Shan; Chen-Yue Li; Guo-Qing Qin; Tong Chen; Qing Wang; Xiang-Gang Hu; Peng-Ju Guo; Hai-Jun Yu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Experimental study on the elastic response characteristics of a rotating body under an oblique water impact load - Shao-Bo Li; Fu-Ren Ming; Tong-Shuai Peng; Yu-Tong Sui (Ocean Engineering, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Eco-friendly and highly efficient PM0.3 air filter made from nonwoven basalt fiber and electrospun nanocellulose fiber - Desalegn Atalie; Ze-Xin Chen; Hui Li; Cun-Guang Liang; Ming-Cheng Gao; Xiao-Xi Cheng; Peng-Cheng Ma (Journal of Hazardous Materials, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Sustainable cottonseed protein bioplastics: Physical and chemical reinforcement, and plant seedling growth application - Hangbo Yue; Xiaodi Li; Lingwei Mai; Qiqi Wu; Ming He; Guoqiang Yin; Jinping Peng; Chufen Yang; Jianwei Guo (Chemical Engineering Journal, 2024)

Confined dual functionalized ionic liquids in metal-organic frameworks for selective NH3 adsorption - Haiyan Jiang; Li Xu; Kuilin Peng; Xiaoling Zhang; Shaojuan Zeng; Yangyang Guo; Lu Bai; Ming-Shui Yao; Xiangping Zhang (Chemical Engineering Journal, 2024)

Ultrahigh-response flexible photothermoelectric photodetectors based on a graded Bi2Te3-carbon nanotube hybrid - Chao Chen; Hai-Long Yu; Yi-Ming Zhao; Peng-Xiang Hou; Shu-Yu Guo; Sheng-Qian Li; Hao-Zike Wang; Kaiping Tai; Chang Liu (Chemical Engineering Journal, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Correction: SETBP1 activation upon MDM4-enhanced ubiquitination of NR3C1 triggers dissemination of colorectal cancer cells - Peng Zhai; Heng Zhang; Qiang Li; Zhifeng Hu; Huaguo Zhang; Ming Yang; Chungen Xing; Yunhu Guo (Clinical & Experimental Metastasis, 2024)

SETBP1 activation upon MDM4-enhanced ubiquitination of NR3C1 triggers dissemination of colorectal cancer cells - Peng Zhai; Heng Zhang; Qiang Li; Zhifeng Hu; Huaguo Zhang; Ming Yang; Chungen Xing; Yunhu Guo (Clinical & Experimental Metastasis, 2024)

CRISPR-Cas9-mediated editing of GmARM improves resistance to multiple stresses in soybean - Tingting Luo; Chongxuan Ma; Yuanhang Fan; Zhendong Qiu; Ming Li; Yusu Tian; Yuzhuo Shang; Chang Liu; Qingqian Cao; Yuhan Peng; Shuzhen Zhang; Shanshan Liu; et al. (Plant Science, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Highly stable planted MXene auxiliary layer for high-performance zinc anode deposition regulation - Qing-peng Bao; Zhuo Li; Bin-bin Sui; Huan Liu; Peng-fei Wang; Zhe Gong; Yu-hang Zhang; Yu-han Wu; Fa-nian Shi; Ming-dong Zhou; Kai Zhu (Chemical Engineering Journal, 2024)

Silk-fibroin-based nanofibrous scaffolds integrated with nano-engineered living bacteria enabling antibiotic-free accelerated infected wound healing - Ming Teng; Xiaomin Luo; Fen Ao; Liuying Li; Jianyan Feng; Peng Zhang; Xiaomeng Zhang; Xudan Liu; Chen Yang; Lufeng Ji; Xuechuan Wang; Haiyan Ju; et al. (Chemical Engineering Journal, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Screening transition metal and nonmetal atoms co-doped graphyne as efficient single-atom catalysts for nitrogen reduction - Shu-Long Li; Ming Peng; Yu Song; Yutao Chen; Liang Qiao; Yong Feng; Yong Zhao; Li-Yong Gan (Chemical Engineering Journal, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Incorporating generative AI agents into socio-economic metabolism modelling: The next frontier - Jianchuan Qi; Jing Guo; Peng Wang; Nan Li; Ming Xu (Resources, Conservation and Recycling, 2024)

Evaluating signal bleaching of Al and Ti–Li centers in fluvio-lacustrine sediments of Datong, North China, and its implications for the volcanic eruption chronology - Hao Ji; Chun-Ru Liu; Wen-Peng Li; Chuan-Yi Wei; Bhupati Neupane; Gong-Ming Yin (Quaternary Geochronology, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

A novel local-drag-force-based approach for simulating wave attenuation by mangrove forests using a 3D-SPH method - Ming Peng; Shuang Li; Liang Gao; Yan Zhu; Jingliang Zhang (Ocean Engineering, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Effects of different curing concentrations and drying times on the microbial community structure and metabolites of dried Spanish mackerel - Jing Li; Yang Liu; Cai-yan Jiang; Xiao-qing Miao; Xiu-ping Dong; Ming Du; Peng-fei Jiang (Food Chemistry, 2024)

Erosion, deposition and breach evolution of landslide dams composed of various dam material types based on flume tests - Chenyi Ma; Ming Peng; Limin Zhang; Zhenming Shi; Jiawen Zhou; Hongxin Chen; Yan Zhu; Zhi Li (Engineering Geology, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

La promoted Ni0-Niδ+ synergistic interaction for rapid and deep hydrogenation of liquid organic hydrogen carriers - Ting Zhu; Li Liu; Yifang Zhao; Min Gao; Yuan Dong; Dong Xia; Peng Huang; Hansong Cheng; Ming Yang (Chemical Engineering Journal, 2024)

Structuring restricted amorphous molecular chains in the reinforced cellulose film by uniaxial stretching - Jing Wang; Shi-Peng Chen; De-Long Li; Lin Zhou; Jia-Xin Ren; Li-Chuan Jia; Gan-Ji Zhong; Hua-Dong Huang; Zhong-Ming Li (Carbohydrate Polymers, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Wogonin preconditioning of MSCs improved their therapeutic efficiency for colitis through promoting glycolysis - Mengye Wu; Cuiping Li; Xue Zhou; Zhiyong Wu; Jianqi Feng; Xiaolu Guo; Rui Fang; Qinghai Lian; Ming Pan; Xiaorong Lai; Yanwen Peng (Inflammopharmacology, 2024)

Replacing soybean meal with fermented rapeseed meal in diets: potential effects on growth performance, antioxidant capacity, and liver and intestinal health of juvenile tilapia (Oreochromis niloticus) - Yaxue Li; Xing Lu; Lixue Dong; Di Peng; Jianmin Zhang; Zongbin Cui; Hua Wen; Juan Tian; Ming Jiang (Fish Physiology and Biochemistry, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Treatment of manganese and lead poisoning with sodium para-aminosalicylic acid: A contemporary update - Yu-Han Xie; Han-Xiao Song; Jian-Chao Peng; Shao-Jun Li; Shi-Yan Ou; Michael Aschner; Yue-Ming Jiang (Toxicology Letters, 2024)

Submerged macrophyte restoration enhanced microbial carbon utilization in shallow lakes - Yao Guo; Songsong Gu; Andrew J. Tanentzap; Pei Wang; Qianzheng Li; Kaixuan Wu; Peng He; Xiangfen Liu; Junqi Yu; Dongru Qiu; Junmei Wu; Yi Zhang; et al. (Science of The Total Environment, 2024)

Comparison and improvement of energy balance establishment methods for heat pretreatment prior to anaerobic digestion - Ming Wang; Kai Liu; Jianlin Wang; Yunting Li; Hao Peng; Lu Ding (Fuel, 2024)

Physicochemical properties and cell viability comparison of two Lactiplantibacillus plantarum DNZ-4 microcapsules and its application in beverages - Cui-Cui Sun; Ming Yi; Yu Miao; Yan Song; Guo-Fang Zhang; Peng Du; Ai-Li Li; Li-Bo Liu; Chun Li (Food Hydrocolloids, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Custom orthotic design by integrating 3D scanning and subject-specific FE modelling workflow - Yinghu Peng; Yan Wang; Qida Zhang; Shane Fei Chen; Ming Zhang; Guanglin Li (Medical & Biological Engineering & Computing, 2024)
The finite element (FE) foot model can help estimate pathomechanics and improve the customized foot orthoses design. However, the procedure of developing FE models can be time-consuming and costly. This study aimed to develop a subject-specific scaled foot modelling workflow for the foot orthoses design based on the scanned foot surface data. Six participants (twelve feet) were collected for the foot finite element modelling. The subject-specific surface-based finite element model (SFEM) was established by incorporating the scanned foot surface and scaled foot bone geometries. The geometric deviations between the scaled and the scanned foot surfaces were calculated. The SFEM model was adopted to predict barefoot and foot-orthosis interface pressures. The averaged distances between the scaled and scanned foot surfaces were 0.23 ± 0.09 mm. There was no significant difference for the hallux, medial forefoot, middle forefoot, midfoot, medial hindfoot, and lateral hindfoot, except for the lateral forefoot region ( p = 0.045). The SFEM model evaluated slightly higher foot-orthoses interface pressure values than measured, with a maximum deviation of 7.1%. These results indicated that the SFEM technique could predict the barefoot and foot-orthoses interface pressure, which has the potential to expedite the process of orthotic design and optimization. Graphical abstract

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Identifying the geospatial relationship of surface ozone pollution in China: Implications for key pollution control regions - Yong Cheng; Yan Peng; Li-Ming Cao; Xiao-Feng Huang; Ling-Yan He (Science of The Total Environment, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Flexible human-machine interface touch system based on double-network solid-state ionic conductive elastomers - Wang Zhan; Qi Zhang; Zhilu Ye; Yuhao Wang; Zihao Yang; Yijing Wang; Cuiling Zhang; Zeying Zhang; Li Xue; Feng Ma; Zhiguang Wang; Niancai Peng; et al. (Chemical Engineering Journal, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

Streptomyces camelliae sp. nov., isolated from rhizosphere soil of Camellia oleifera Abel - Zheng Yaxi; Deng Aihua; Xu Xiaoxiao; Li Chenxi; Peng Yi; Tang Ting; Liu Jin; Ming Yiru; Mo Ping (Archives of Microbiology, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Climate warming impacts chewing Spodoptera litura negatively but sucking Corythucha marmorata positively on native Solidago canadensis - Xiao-Hui Zhou; Jing-Ji Li; Pei-Hao Peng; Wei-Ming He (Science of The Total Environment, 2024)

Numerical simulation analysis of stable flow of hydrate slurry in gas-liquid-solid multiphase flow - Xiao-Fang Lv; Kai-Yue Xu; Yang Liu; Chuan-Shuo Wang; Ming-Guo Peng; Hui Du; Shuang-Cindy Cao; Qian-Li Ma; Shi-dong Zhou; Shang-Fei Song (Ocean Engineering, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Rational biodiesel production from oxidation stability perspective: Evaluation of lipid-soluble carbonyl compound formation in the seed oil and biodiesel with long-term storage - Xiao-Hui Peng; Hua-Ming Xiao; Shuai Zhao; Dilshad Hussain; Jian-Li Chen; Dan Luo; Dan Wang; Xin Lv; Xian Wang; Hong Chen; Fang Wei (Fuel, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Initial study and phylogenetic analysis of hard ticks (Acari: Ixodidae) in Nantong, China along the route of avian migration - Jian-Ming Yuan; Jing Su; Zhi-Hai Zhang; Bin Sun; Xue-Li Jiao; Xin Zhang; Yun-Peng Zhai; Yu-Jie Chen (Experimental and Applied Acarology, 2024)

Biogenic manganese oxides promote metal(loid) remediation by shaping microbial communities in biological aqua crust - Guobao Wang; Zekai Feng; Xiuran Yin; Daijie Chen; Nan Zhao; Yongqiang Yuan; Chiyu Chen; Chong Liu; Ming Ao; Lei Chen; Ziwu Chen; Wenjun Yang; et al. (Water Research, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Evolution of high-filling loess slope under long-term seasonal fluctuation of groundwater - Han Bao; Li Liu; Hengxing Lan; Jianbing Peng; Changgen Yan; Ming Tang; Guanmiao Guo; Han Zheng (CATENA, 2024)

Effects of Dietary Fish Meal Replaced by Cottonseed Protein Concentrate on Growth Performance, Antioxidant Capacity, and Liver and Intestinal Health of Juvenile Hybrid Culter - Guangming Xu; Huijie Wei; Di Peng; Lang Zhang; Xing Lu; Qing Li; Lixue Dong; Juan Tian; Hua Wen; Guiying Wang; Ming Jiang (Fishes, 2024)
The objective of this study was to assess the impact of concentrated cottonseed protein (CPC) as a substitute for fishmeal (FM) in juvenile hybrid culter (Erythroculter ilishaeformis ♀ × Ancherythroculter nigrocauda ♂). A total of 360 fish with an initial body weight of 10.0 ± 0.5 g were randomly allocated into 12 indoor culture tanks, with each tank containing 30 fish. Four diets were formulated in which fish meal (FM) was replaced by CPC at different inclusion levels: 0% (T0), 15% (T15), 30% (T30), and 45% (T45). The corresponding amounts of CPC included were 0, 61, 122, and 182 g/kg, respectively. At the end of the 10-week feeding trial, the findings revealed an inverse correlation between the proportion of CPC replacing FM and both final body weight (FBW) and weight growth rate (WG) in hybrid culter. Specifically, the T30 and T45 groups exhibited significantly lower FBW and WG compared to the T0 group (p 0.05). However, the crude lipid content was highest in hybrid culter fed the T45 diet and lowest in the T0 group (p 0.05). The contents of total protein (TP) and albumin (ALB) declined slightly as the proportion of FM substituted by CPC increased, yet this decline did not reach statistical significance (p > 0.05). Serum alanine aminotransferase (ALT) activity elevated with increasing dietary CPC, and the T45 group exhibited significantly higher ALT activity compared to the T0 group (p

Miocene Equisetum tubers from the Wulan Basin, Northeast Qinghai-Tibetan Plateau and their paleoecological significance - Zhen-Dong Cao; Peng Zhang; Si-Hang Zhang; Yi-Hong Yang; Jia-Yi Chen; Li-Ming Liu; Xiang-Chuan Li; San-Ping Xie (Palaeoworld, 2024)

Efficient degradation of imidacloprid by surface discharge cold plasma: Mechanism of interaction between ROS and molecular structure and evaluation of residual toxicity - Jia-Bao Ni; Xiao-Fang Jia; Jun-Ying Zhang; Chang-Jiang Ding; Wen-Li Tian; Wen-Jun Peng; Sara Zielinska; Hong-Wei Xiao; Xiao-Ming Fang (Journal of Hazardous Materials, 2024)

Bimetal MOF-derived NiFe-P nanocomposites coupled with Cu3P nanoparticles to construct tandem electron transfer channels for photocatalytic hydrogen evolution - Haiyan Zhang; Shitao Yang; Peng Zhu; Senpei Tang; Ming Li (Journal of Environmental Sciences, 2024)

A novel deep learning framework for landslide susceptibility assessment using improved deep belief networks with the intelligent optimization algorithm - Shaoqiang Meng; Zhenming Shi; Gang Li; Ming Peng; Liu Liu; Hongchao Zheng; Changshi Zhou (Computers and Geotechnics, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Evolution model and failure mechanisms of rainfall-induced cracked red clay slopes: insights from Xinshao County, China - Weizhi Jiao; Ming Zhang; Peng Li; Junjin Xie; Haisong Pang; Fuxing Liu; Long Yang (Journal of Mountain Science, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Characteristics of ash formed by different lubricant additives and its effect on DPF performance - Pi-qiang Tan; Tian-peng Liu; Li-shuang Duan; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Experimental and numerical study on the breaching mechanisms of landslide dams with non-uniform structures - Xianrui Hu; Xiaoli Fu; Ming Peng; Gongding Zhang; Zhenming Shi; Yan Zhu; Yuchun Li (Engineering Geology, 2024)

Two-phase modelling of erosion and deposition process during overtopping failure of landslide dams using GPU-accelerated ED-SPH - Mingjun Zhou; Zhenming Shi; Chong Peng; Ming Peng; Kahlil Fredrick E. Cui; Bo Li; Limin Zhang; Gordon G.D. Zhou (Computers and Geotechnics, 2024)

Dual nonionic photoacids synergistically enhanced photosensitivity for chemical amplified resists - Ling-Yan Peng; Shi-Li Xiang; Jun-Dan Huang; Ying-Yi Ren; Pan Hong; Chong Li; Jun Liu; Ming-Qiang Zhu (Chemical Engineering Journal, 2024)

In-situ sodium chloride template synthesis of γ-WO3 hollow cubes for high-sensing and dual-selective hydrazine/dibutylamine detection at different temperatures - Guo-Li Chen; Ming-Song Lv; Jing Zhang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Myricetin-based fluorescence probes with AIE and ESIPT properties for detection of hydrazine in the environment and fingerprinting - Wei Xiao; Qing Zhang; Dong Hui You; Wei Xue; Feng Peng; Nian Bing Li; Guang Ming Zhou; Hong Qun Luo (Analytica Chimica Acta, 2024)

A Deep-Sea Environment Simulated Test System for Subsea Control Modules, Part A: Prototype and Test - Shoubo Shang; Xiangyu Wang; Qingnan Han; Peng Jia; Feihong Yun; Jing Wen; Chao Li; Ming Ju; Liquan Wang (Journal of Marine Science and Engineering, 2024)
This paper proposes a version of the deep-sea environment simulated test system for subsea control modules to solve the problem of incomplete testing systems for electro-hydraulic subsea control modules. Based on the subsea control module test requirements specified in APISTD17F, the test system in this paper is a highly integrated system, including a test hydraulic power unit, a control module test bench, a signal simulator, an electronic test unit, an umbilical simulator, a high-pressure chamber, and an incubator. Firstly, the design indicators of the test system were determined by analyzing the various functions of the subsea control module and its working environment. Secondly, the design scheme for the test system was proposed, and a detailed design was carried out. Finally, a hydro-electrical subsea control module for the Bohai Sea was fully tested with this system, with tests including the qualification test and the factory acceptance test. The test results show that all parts of the test system coordinated well and have achieved the design indicators, and the test system can simulate the working environment and complete a land test. The effectiveness and feasibility of the test system have been verified through the test. By adopting this system, the risk of subsea control module failure can be minimized, laying the foundations for future research and improvement of subsea control module testing equipment.

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

High alumina basalts identification and their feature analysis in Mare Fecunditatis - Ming Ma; Jingran Chen; Shengbo Chen; Bingze Li; Chenghao Han; Peng Tian (Icarus, 2024)

Effects of lubricant components on ash-bridge deposition characteristics in the diesel particulate filter - Pi-qiang Tan; Yuan Tian; Li-shuang Duan; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Large-area nanofiber membrane of NIR photothermal Cs0.32WO3 for flexible and all-weather solar thermoelectric generation - Sheng Zhuo; Wangkai Jiang; Yu Dong Zhao; Jin-Zhuo Liu; Xinyu Zhao; Jianyong Ye; Min Zheng; Zuo-Shan Wang; Xiao-Qing Zhou; Xiao-Qiao Wang; Ying-Li Shi; Weifan Chen; et al. (Chemical Engineering Journal, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Structure, function and immune evasion strategies of aquareoviruses, with focus on grass carp reovirus - Peng Wei Li; Jie Zhang; Ming Xian Chang (Reviews in Aquaculture, 2024)
Aquareoviruses (AqRVs) can infect various wild or cultured bony fishes with serious muscle and viscera haemorrhage syndrome and have caused severe economic losses worldwide. Accumulating evidences have revealed the functions of viral proteins of AqRVs in RNA transcription, virion assembly, cell attachment and/or viral replication. In addition, structural information and transcription mechanism of AqRVs have been in‐depth studied through cryo‐electron microscopy combined with three‐dimensional image reconstruction. Although far from enough, structural and functional studies of AqRVs provide substantial insights into how viral proteins coordinate the replication of AqRVs and escape the host immune response. Grass carp reovirus (GCRV) is the most pathogenic AqRV isolated from aquatic animals. The completion of GCRV lifecycle requires the participation of host proteins. So far, many host factors involved in the entry and replication of GCRV have been identified. Based on the function of viral proteins and the viral lifecycle, many vaccines and antiviral agents have been developed to prevent the replication and infection of GCRV. This review summarises the structural characteristics and the composition of core proteins of AqRVs, as well as synergistic mechanisms of structural proteins on genome transcription and virus entry of AqRVs. In addition, the review highlights our current knowledge for the infection and replication, functions of non‐structural proteins, immune escape mechanisms, as well as the vaccines and antiviral agents of AqRVs, especially for GCRV. A better understanding of structure, function and immune evasion strategies of AqRVs will offer new targets for prevention and control of AqRVs in aquaculture.

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Quantitative proteomics reveals the neurotoxicity of trimethyltin chloride on mitochondria in the hippocampus of mice - Zhenzhong Liu; Li Wang; Yue Wang; Siya Wu; Caiting Peng; Yu Wang; Ming Huang; Li Che; Rongjing Sun; Xi Zhao; Zuo Du; Wenhu Liu (NeuroToxicology, 2023)

Physicochemical characteristics of ash-bridges in diesel particulate filter - Li-shuang Duan; Pi-qiang Tan; Yun-peng Li; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

The 10 Most Influential Heavy Rain Events in China in 2022: Selection and Evaluation - Ao Li; Hao Yang; Chunguang Cui; Tao Peng; Yishan Liao; Ming Xu; Xiaofang Wang (Journal of Meteorological Research, 2023)

Study on Improving the Performance of Traditional Medicine Extracts with High Drug Loading Based on Co-spray Drying Technology - Zhe Li; Wanghai Peng; Lin Zhu; Wenjun Liu; Lingyu Yang; Lihua Chen; Abid Naeem; Weifeng Zhu; Yi Feng; Liangshan Ming (AAPS PharmSciTech, 2023)

Adsorption-desorption behaviors of ciprofloxacin onto aged polystyrene fragments in aquatic environments - Xiao-Yang Liu; Ning Wang; Long-Yi Lv; Peng-Fei Wang; Wen-Fang Gao; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemosphere, 2023)

Key drivers to heterogeneity evolution of black carbon-containing particles in real atmosphere - Yan Peng; Li-Ming Cao; Jing Wei; Yong Cheng; Kuangyou Yu; Ke Du; Xiao-Feng Huang (Science of The Total Environment, 2023)

Sedimentary facies and chronological study for a Late Pleistocene sand layer with swash cross bedding within a sand hill at north of Poyang Lake, as inferred from sedimentary structure and optical dating of K-feldspar and quartz grains - Zhijun Gong; Qiwei Li; Ming Luo; Chaocheng Dai; Huaming Peng (Quaternary International, 2023)

Effect of electrohydrodynamic drying on bee pollen biochemical pathways - Jia-Bao Ni; Yin-Chen Wang; Hong-Wei Xiao; Sara Zielinska; Wen-Li Tian; Xiang-Xin Li; Wen-Jun Peng; Xiao-Ming Fang (Journal of Cleaner Production, 2023)

Effect of ash on temperature and particulate emission characteristics of diesel particulate filter during active regeneration - Li-shuang Duan; Pi-qiang Tan; Yi-fan Yin; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Characterizing nighttime vertical profiles of atmospheric particulate matter and ozone in a megacity of south China using unmanned aerial vehicle measurements - Zhanyong Wang; Ruhui Cao; Bai Li; Ming Cai; Zhong-Ren Peng; Guohua Zhang; Qingchang Lu; Hong-di He; Jinpu Zhang; Kai Shi; Yonghong Liu; Hui Zhang; et al. (Environmental Research, 2023)

Tailor-made yolk-shell nanocomposites of star-shape Au and porous organic polymer for nitrogen electroreduction to ammonia - Hongming He; Hao-Ming Wen; Ping Li; Hong-Kai Li; Cheng-Peng Li; Zhihong Zhang; Miao Du (Chemical Engineering Journal, 2023)

Regulation of renal lipid deposition in diabetic nephropathy on morroniside via inhibition of NF-KB/TNF-a/SREBP1c signaling pathway - Wenhui Zhu; Ming Chen; Yang Wang; Yao Chen; Yonggang Zhang; Yan Wang; Peng Liu; Ping Li (Chemico-Biological Interactions, 2023)

Introgression of the bread wheat D genome encoded Lr34/Yr18/Sr57/Pm38/Ltn1 adult plant resistance gene into Triticum turgidum (durum wheat) - Hongyu Li; Peng Zhang; Ming Luo; Mohammad Hoque; Soma Chakraborty; Brenton Brooks; Jianbo Li; Smriti Singh; Kerrie Forest; Allan Binney; Lianquan Zhang; Diane Mather; et al. (Theoretical and Applied Genetics, 2023)
Key Message Lack of function of a D-genome adult plant resistance gene upon introgression into durum wheat. Abstract The wheat Lr34/Yr18/Sr57/Pm38/Ltn1 adult plant resistance gene ( Lr34 ), located on chromosome arm 7DS, provides broad spectrum, partial, adult plant resistance to leaf rust, stripe rust, stem rust and powdery mildew. It has been used extensively in hexaploid bread wheat (AABBDD) and conferred durable resistance for many decades. These same diseases also occur on cultivated tetraploid durum wheat and emmer wheat but transfer of D genome sequences to those subspecies is restricted due to very limited intergenomic recombination. Herein we have introgressed the Lr34 gene into chromosome 7A of durum wheat. Durum chromosome substitution line Langdon 7D(7A) was crossed to Cappelli ph1c , a mutant derivative of durum cultivar Cappelli homozygous for a deletion of the chromosome pairing locus Ph1 . Screening of BC 1 F 2 plants and their progeny by KASP and PCR markers, 90 K SNP genotyping and cytology identified 7A chromosomes containing small chromosome 7D fragments encoding Lr34 . However, in contrast to previous transgenesis experiments in durum wheat, resistance to wheat stripe rust was not observed in either Cappelli/Langdon 7D(7A) or Bansi durum plants carrying this Lr34 encoding segment due to low levels of Lr34 gene expression. Key message

Advances and Applications of Brain Organoids - Yang Li; Peng-Ming Zeng; Jian Wu; Zhen-Ge Luo (Neuroscience Bulletin, 2023)
Understanding the fundamental processes of human brain development and diseases is of great importance for our health. However, existing research models such as non-human primate and mouse models remain limited due to their developmental discrepancies compared with humans. Over the past years, an emerging model, the “brain organoid” integrated from human pluripotent stem cells, has been developed to mimic developmental processes of the human brain and disease-associated phenotypes to some extent, making it possible to better understand the complex structures and functions of the human brain. In this review, we summarize recent advances in brain organoid technologies and their applications in brain development and diseases, including neurodevelopmental, neurodegenerative, psychiatric diseases, and brain tumors. Finally, we also discuss current limitations and the potential of brain organoids.

Role of sonic hedgehog signaling pathway in the regulation of ion channels: focus on its association with cardio-cerebrovascular diseases - Ming-Rui Li; Xiu-Ju Luo; Jun Peng (Journal of Physiology and Biochemistry, 2023)

Nine pairs of undescribed enantiomers from the resin of Styrax tonkinensis (Pierre) Craib ex Hart with anti-inflammatory activity - Qun Li; Hong-Bin Fang; Bin-Yuan Hu; Yong-Ming Yan; Ya-Bin Jiao; Gan-Peng Li; Yong-Xian Cheng (Phytochemistry, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Experimental study on visualization of TBAB hydrate formation in confined small channels - Qi-Rong Zuo; Ming Gao; Peng Kong; Li-Xin Zhang (Fuel, 2023)

Preparation and identification of novel antioxidant peptides from camel bone protein - Jianing Wang; Geng Yang; Hanfeng Li; Tong Zhang; Di Sun; Wei Peng Lu; Weijie Zhang; Yihu Wang; Ming Ma; Xiaofeng Cao; Bing Zhang; Yanchuan Guo (Food Chemistry, 2023)

Lignin micro/nanoparticles: synthesis, properties, and application to endow polyvinyl alcohol film with multi-functionality - Ying-Hong Xu; Ming-Fei Li; Feng Peng (Chemical Engineering Journal, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Distribution of iodine concentration in drinking water in China mainland and influence factors of its variation - Xin Hou; Meng Zhao; Jia Li; Yang Du; Ming Li; Lixiang Liu; Peng Liu; Fangang Meng; Lijun Fan; Hongmei Shen; Dianjun Sun (Science of The Total Environment, 2023)

One-stage partial nitrification/anammox system with short sludge retention time and low mixed liquor suspended solids long-term control: Establishment, performance and sludge characteristics - Cong Wang; Li-Fang Liu; Shu-Jun Zhang; Zhi-Ming Qu; Wei-Kang Qi; Yong-Zhen Peng (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Assessment of dynamic drought-induced ecosystem risk: Integrating time-varying hazard frequency, exposure and vulnerability - Wei Fang; Qiang Huang; Gordon Huang; Bo Ming; Quan Quan; Pei Li; Yi Guo; Xudong Zheng; Gang Feng; Jian Peng (Journal of Environmental Management, 2023)

Pathways to increase maize yield in Northwest China: A multi-year, multi-variety analysis - Yugang Wang; Guoqiang Zhang; Rongfa Li; Keru Wang; Bo Ming; Peng Hou; Ruizhi Xie; Jun Xue; Shaokun Li (European Journal of Agronomy, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Variations and driving mechanisms of desertification in the southeast section of the China-Mongolia-Russia Economic Zone - Yonghua Zhao; Shuyuan Yang; Li Liu; Xia Jia; Lei Han; Xuefeng Yuan; Ming Zhao; Peng Zhang (Science of The Total Environment, 2023)

Quantum computer-aided design for advanced superconducting qubit: Plasmonium - Feng-Ming Liu; Can Wang; Ming-Cheng Chen; He Chen; Shao-Wei Li; Zhong-Xia Shang; Chong Ying; Jian-Wen Wang; Yong-Heng Huo; Cheng-Zhi Peng; Xiaobo Zhu; Chao-Yang Lu; et al. (Science Bulletin, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Biological function research of Fusarium oxysporum f. sp. cubense inducible banana long noncoding RNA Malnc2310 in Arabidopsis - Wenbin Li; Pingjuan Zhao; Jianbo Sun; Xiaoling Yu; Liangping Zou; Shuxia Li; Rong Di; Mengbin Ruan; Ming Peng (Plant Molecular Biology, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Critical Metals Ga, Ge and In in the Global Pb-Zn Deposits: Current Understanding, Challenges and Perspectives - Yi Zheng; Peng-Peng Yu; Zhan-Ke Li; Suo-Fei Xiong; Ling-Li Zhou; Jia-Xi Zhou; Chang-Ming Wang; Yu-Miao Meng; Yu Zhang; Ye-Jian Wang; Jing Xu; Yue Wu; et al. (Journal of Earth Science, 2023)

Reducing plastic film mulching and optimizing agronomic management can ensure food security and reduce carbon emissions in irrigated maize areas - Guoqiang Zhang; Bo Ming; Ruizhi Xie; Jianglu Chen; Peng Hou; Jun Xue; Dongping Shen; Rongfa Li; Juan Zhai; Yuanmeng Zhang; Keru Wang; Shaokun Li (Science of The Total Environment, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Exploring the potential of metal oxides as cathodic catalysts in a double chambered microbial fuel cell for phenol removal and power generation - Kea-Lee Yap; Li-Ngee Ho; Kun Guo; Yun-Ming Liew; Nabilah Aminah Lutpi; Ayu Wazira Azhari; Shen-Hui Thor; Tean-Peng Teoh; Yoong-Sin Oon; Soon-An Ong (Journal of Water Process Engineering, 2023)

Serum thyroglobulin as a biomarker of iodine excess and thyroid disease occurrence in adults - Yang Du; Peng Liu; Wei Zhang; Jinyin Yao; Fangang Meng; Lijun Fan; Lixiang Liu; Ming Li; Chunpeng Lv; Wen Jiang; Dianjun Sun (Journal of Trace Elements in Medicine and Biology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

A system for inspecting karst voids during construction of cast-in-place pile foundations - Liu Liu; Zhenming Shi; Shaojun Li; Ming Peng; Fengjuan Tao (Engineering Geology, 2023)

Molecular detection of Nocardia: development and application of a real-time PCR assay in sputum and bronchoalveolar lavage fluid samples - Shuai Wang; Peng Wang; Jun Liu; Chunxia Yang; Tianmeng Li; Jingxian Yang; Li Gu; Ming Wei (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Slope stability under the influence of irrigation and frozen stagnant water effect in Heifangtai - Guang Li; Ming-gao Tang; Ming-li Zhang; Da-lei Peng; Huan-le Zhao; Jian Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Aspergillus niger confers health benefits and modulates the gut microbiota of juvenile Pacific white shrimp (Penaeus vannamei) under farming conditions - Ming Zhang; Huifen Liang; Yifan Lei; Yiwen Zhang; Zhigang Tan; Wenzhen Chen; Shengkang Li; Xianfeng Peng; Ngoc Tuan Tran (Frontiers in Marine Science, 2023)
Introduction The fungus Aspergillus niger is found to be predominant in the body of Pacific white shrimp ( Penaeus vannamei ); however, its role in shrimp’s health has not been explored. This study aimed to evaluate the influences of A. niger on growth, antioxidative activity, immune response, and gut microbiota of juvenile Pacific white shrimps under farming conditions. Methods Shrimps (2.30±1.05 g) were fed diets supplemented with 0 (control), 1.5 (A1.5), or 3.0 g/kg diet of A. niger (A3.0) for one month. At the end of the study, the growth, antioxidant enzyme activity and immune parameters, and gut microbiota in shrimps fed with different experimental diets were analyzed. Results The results showed a significant increase in weight gain, specific growth rate, and length gain of shrimps in A1.5, compared with other groups ( P <0.05). With the exception of lysozyme in both A1.5 and A3.0, which were lower than in the control, the activity of superoxide dismutase (SOD), catalase, acid phosphatase, alkaline phosphatase, and phenol oxidase was higher than those in the control. Gene expressions of SOD, anti-lipopolysaccharide factor-ALF1, and ALF2 (in A1.5 and A3.0) and nitric oxide synthase, penaeidin-PEN2 (in A1.5) and PEN3 and PEN4 (in A3.0) were significantly up-regulated compared to the control ( P <0.05). The addition of A. niger increased diversity and separated the microbial community in the gut of shrimps. At the phylum level, Firmicutes and Bacteroidota were dominant, and Proteobacteria was less abundant in the A1.5 and A3.0, as compared to the control. At the genus level, the relative abundance of Vibrio, Marivita , and Roseobacter was increased but Ruegeria was decreased in A1.5 and A3.0 when compared to the control. The genera Edwardsiella, Clostridium sensu stricto 1 , and Shimia in the A1.5 were higher than in the control. Discussion These findings demonstrated the beneficial effects of A. niger on growth, health, and changes in the gut microbiota in shrimps under farming conditions. The recommended concentration of A. niger in the diet for shrimps is 1.5 g/kg diet.

Inulin acetate as a novel recombinant subunit vaccine carrier for immunization of tilapia against tilapia lake virus - Yu-Ying Zheng; Yang Li; Tian-Zi Sun; Xue-Feng Wei; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Bin Zhu (Aquaculture, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

Effects of adsorption characteristics of carbocatalysts on persulfate-based advanced oxidation processes: Organic removal mechanisms and optimization strategies - Xiang-Feng Huang; Jing-Xi Yuan; Xia Zhao; Shuang-Qiang Li; Li-Heng Yang; Wen-Yan Li; Kai-Ming Peng; Chen Cai; Jia Liu (Chemical Engineering Journal, 2023)

Schisandrin B Improves the Hypothermic Preservation of Celsior Solution in Human Umbilical Cord Mesenchymal Stem Cells - Ying Zhang; Peng Wang; Mei-xian Jin; Ying-qi Zhou; Liang Ye; Xiao-juan Zhu; Hui-fang Li; Ming Zhou; Yang Li; Shao Li; Kang-yan Liang; Yi Wang; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Numerical simulation of rockburst disaster and control strategy of constant resistance and large deformation anchor cable in Gaoloushan tunnel - Cheng-yu Miao; Ming Jiang; Zhi-hu Li; Xiao-ming Sun; Tong Zhang; Yong Zhang; Jin-kun Yang; Chao Ren; Peng Song (Journal of Mountain Science, 2023)

Retraction Note to: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2023)

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Low-temperature and dual-sensing NO2/dimethylamine sensor based on single-crystal WO3 nanoparticles-supported sheets synthesized by simple pyrolysis of spoiled WCl6 powder - Guo-Li Chen; Ming-Song Lv; Li-Li Sui; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

OsPEX1, an extensin-like protein, negatively regulates root growth in a gibberellin-mediated manner in rice - Jieni Li; Yuexiong Zhang; Zhenyong Li; Hang Dai; Xin Luan; Tianxiu Zhong; Shu Chen; Xin-Ming Xie; Gang Qin; Xiang-Qian Zhang; Haifeng Peng (Plant Molecular Biology, 2023)

Early 7,8-Dihydroxyflavone Administration Ameliorates Synaptic and Behavioral Deficits in the Young FXS Animal Model by Acting on BDNF-TrkB Pathway - Yu-shan Chen; Si-ming Zhang; Wei Tan; Qiong Zhu; Chao-xiong Yue; Peng Xiang; Jin-quan Li; Zhen Wei; Yan Zeng (Molecular Neurobiology, 2023)

HSF4 promotes tumor progression of colorectal cancer by transactivating c-MET - Wenjing Zhang; Xuelian Zhang; Peng Cheng; Kelin Yue; Ming Tang; Yan Li; Qiang Guo; Yu Zhang (Molecular and Cellular Biochemistry, 2023)

Functional differentiation of two general odorant-binding proteins to sex pheromones in Spodoptera frugiperda - Hui-Hui Yang; Shu-Peng Li; Mao-Zhu Yin; Xiu-Yun Zhu; Jin-Bu Li; Ya-Nan Zhang; Xiao-Ming Li (Pesticide Biochemistry and Physiology, 2023)

Effect of lithofacies on differential movable fluid behaviors of saline lacustrine fine-grained mixed sedimentary sequences in the Jimusar sag, Junggar Basin, NW China: Forcing mechanisms and multi-scale models - Wei Yang; Yaohua Wang; Ming Xie; Yingyan Li; Yang Gao; Yuan Deng; Changfu Xu; Jianhua Qin; Shouchang Peng; Leilei Yang; Linjie Yao; Haodong Hou (Marine and Petroleum Geology, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Biofilter-constructed wetland-trophic pond system: A new strategy for effective sewage treatment and agricultural irrigation in rural area - Xinxin Peng; Wei Yang; Qiu Jin; Shihua Su; Pan Guo; Ming Li; Huazu Liu; Wei Li (Journal of Environmental Management, 2023)

In-situ treatment of an end of rivers by autotrophic/ heterotrophic nitrification and aerobic denitrification (HN-AD) membrane aerated biofilm reactors (MABRs) - Ming Li; Cuicui Cao; Yi Li; Xinglin Li; Boyang Hu; Ziqing Wu; Peng Zhang; Hong Guo; Baoan Li (Journal of Environmental Chemical Engineering, 2023)

Devonian subduction retreat recorded in the Chinese Altai Orogen: Petro-structural and geochronological constraints from orogenic lower crust migmatite-granite complexes - Ling-Zhu Kong; Ying-De Jiang; Peng-Fei Li; Stephen Collett; Ming Xiao (Journal of Asian Earth Sciences, 2023)

Development, calibration and validation of a phase-averaged model for cross-shore sediment transport and morphodynamics on a barred beach - Peng Zheng; Gugum Gumbira; Ming Li; Joep van der Zanden; Dominic van der A; Jebbe van der Werf; Xueen Chen; Xiaonan Tang (Continental Shelf Research, 2023)

Rapid room-temperature polymerization strategy to prepare organic/inorganic hybrid conductive organohydrogel for terahertz wave responsiveness - Haihan Zou; Peng Yi; Wenbin Xu; He Cai; Junzhe He; Xin Sun; Xufeng Li; Chunyan Chen; Gao Deng; Yingbo Yuan; Zhenyang Li; Ming Fang; et al. (Chemical Engineering Journal, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Sensitive detection of viable salmonella bacteria based on tertiary cascade signal amplification via splintR ligase ligation-PCR amplification-CRISPR/Cas12a cleavage - Changyu Zhou; Wenjing Li; Yu Zhao; Kui Gu; Ziwei Liao; Boyan Guo; Zheren Huang; Ming Yang; Hongcheng Wei; Peng Ma; Chao Li; Hao Li; et al. (Analytica Chimica Acta, 2023)

Hydroquinone triggers pyroptosis and endoplasmic reticulum stress via AhR-regulated oxidative stress in human lymphocytes - Xiaohan Yang; Shuangyan Dong; Chao Li; Ming Li; Caihong Xing; Jin He; Cheng Peng; Hua Shao; Qiang Jia (Toxicology Letters, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

Research on the Purification Performance of a Floating Island System Treating the Effluent of WWTP Under Different Seasons - Zhao-xu Peng; Ning-qi Niu; Ting-mei Li; Lu-ji Yu; Li-kun Gu; Ming-hui Liu (Water, Air, & Soil Pollution, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Momordica charantia polysaccharide ameliorates D-galactose-induced aging through the Nrf2/β-Catenin signaling pathway - Jun Yue; Peng Guo; Yuexinzi Jin; Ming Li; Xiaotong Hu; Wan Wang; Xuewen Wei; Suhua Qi (Metabolic Brain Disease, 2023)

Agricultural nitrate export patterns shaped by crop rotation and tile drainage - Zewei Ma; Kaiyu Guan; Bin Peng; Murugesu Sivapalan; Li Li; Ming Pan; Wang Zhou; Richard Warner; Jingwen Zhang (Water Research, 2023)

Distribution and drivers of antibiotic resistance genes in brackish water aquaculture sediment - Chao Li; Hao-qiang Chen; Peng Gao; Xing-hao Huang; Yun-xiang Zhu; Ming Xu; Quan Yuan; Yuan Gao; Xiao-xiao Shen (Science of The Total Environment, 2023)

Characterizing formation mechanisms of secondary aerosols on black carbon in a megacity in South China - Jing Wei; Ying-Bo Niu; Meng-Xue Tang; Yan Peng; Li-Ming Cao; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2023)

Applications of functional nanoparticle–stabilized surfactant foam in petroleum-contaminated soil remediation - Jia Liu; Wen-yan Li; Hong-xin Chen; Shuang-qiang Li; Li-heng Yang; Kai-ming Peng; Chen Cai; Xiang-feng Huang (Journal of Hazardous Materials, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Evaluating the influence of gradient applied voltages on electro-enhanced sequence batch reactor treating aniline wastewater: System performance, microbial community and functional genes - Jing He; Qian Zhang; Meng Li; Tingzhen Ming; Jiapeng Feng; Haojin Peng; Junhao Su; Yunjie Zhang (Journal of Cleaner Production, 2023)

Sesamol alleviates manganese-induced neuroinflammation and cognitive impairment via regulating the microglial cGAS-STING/NF-κB pathway - Jinxia Wu; Honggang Chen; Tingting Guo; Ming Li; Changhao Yang; Michael Aschner; Jingyuan Chen; Peng Su; Wenjing Luo (Environmental Pollution, 2023)

Photoactivatable metal organic framework for synergistic ferroptosis and photodynamic therapy using 450 nm laser - Yuhang Chen; Lijiang Gu; Bohan Ma; Xing Li; Yibo Mei; Jinlai Zhou; Yue Chong; Minghai Ma; Mengzhao Zhang; Lu Wang; Yifan Cheng; Kaijie Wu; et al. (Chemical Engineering Journal, 2023)

Boosting the hydrogen evolution of layered double hydroxide by optimizing the electronic structure and accelerating the water dissociation kinetics - Hongbo He; Jiayong Xiao; Zhibin Liu; Bin Yang; Dashuai Wang; Xianyun Peng; Libin Zeng; Zhongjian Li; Lecheng Lei; Ming Qiu; Yang Hou (Chemical Engineering Journal, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Pyrite trace element and S-Pb isotopic evidence for contrasting sources of metals and ligands during superimposed hydrothermal events in the Dongping gold deposit, North China - Huan Li; Da-Peng Zhu; Thomas J. Algeo; Ming Li; Wei-Cheng Jiang; She-Fa Chen; Safiyanu Muhammad Elatikpo (Mineralium Deposita, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

A global analysis of dry matter accumulation and allocation for maize yield breakthrough from 1.0 to 25.0 Mg ha−1 - Guangzhou Liu; Yunshan Yang; Xiaoxia Guo; Wanmao Liu; Ruizhi Xie; Bo Ming; Jun Xue; Keru Wang; Shaokun Li; Peng Hou (Resources, Conservation and Recycling, 2023)

Technological development pathway for carbon neutrality in China - Siyue Guo; Yu Liu; Weichen Zhao; Jiaquan Li; Guangwen Hu; Hui Kong; Yifan Gu; Bang Xu; Xiaodan Huang; Yan Zheng; Shihan Zhang; Da Zhang; et al. (Science Bulletin, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Ketamine modulates neural stem cell differentiation by regulating TRPC3 expression through the GSK3β/β-catenin pathway - Ying-Jun She; Junping Pan; Liang-Ming Peng; Li Ma; Xinying Guo; Dong-Xu Lei; Huai-Zhen Wang (NeuroToxicology, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Cellulose mineralization with in-situ synthesized amorphous titanium dioxide for enhanced adsorption and auto-accelerating photocatalysis on water pollutant - Jin-Long Zhu; Shi-Peng Chen; Wei Lin; Hua-Dong Huang; Zhong-Ming Li (Chemical Engineering Journal, 2023)

Patternable thermal conductive interface materials enabled by vitrimeric phase change materials - Li-Mei Peng; Zhao Xu; Jie Yang; Lu Bai; Rui-Ying Bao; Ming-Bo Yang; Wei Yang (Chemical Engineering Journal, 2023)

Water-in-zircon: a discriminant between S- and I-type granitoid - Jing Mo; Xiao-Ping Xia; Peng-Fei Li; Christopher J. Spencer; Chun-Kit Lai; Jian Xu; Qing Yang; Ming-Dao Sun; Yang Yu; Luke Milan (Contributions to Mineralogy and Petrology, 2023)

Guanine nucleotide-binding protein 2, GNBP2, accelerates the progression of clear cell renal cell carcinoma via regulation of STAT3 signaling transduction pathway - Qingfei Cao; Jiaji Ma; Weitao Li; Peng Hong; Tong Shen; Ming Tong (Genes & Genomics, 2023)

Seasonal variability of eddy kinetic energy in the East Australian current region - Jia Liu; Shaojun Zheng; Ming Feng; Lingling Xie; Baoxin Feng; Peng Liang; Lei Wang; Lina Yang; Li Yan (Frontiers in Marine Science, 2022)
The East Australian Current (EAC) is an important western boundary current of the South Pacific subtropical Circulation with high mesoscale eddy kinetic energy (EKE). Based on satellite altimeter observations and outputs from the eddy-resolving ocean general circulation model (OGCM) for the Earth Simulator (OFES), the seasonal variability of EKE and its associated dynamic mechanism in the EAC region are studied. High EKE is mainly concentrated in the shear-region between the poleward EAC southern extension and the equatorward EAC recirculation along Australia's east coast, which is confined within the upper ocean (0-300 m). EKE in this area exhibits obvious seasonal variation, strong in austral summer with maximum (465±89 cm² s-²) in February and weak in winter with minimum (334±48 cm² s-²) in August. Energetics analysis from OFES suggests that the seasonal variability of EKE is modulated by the mixed instabilities composed of barotropic and baroclinic instabilities confined within the upper ocean, and barotropic instability (baroclinic instability) is the main energy source of EKE in austral summer (winter). The barotropic process is mainly controlled by the zonal shear of meridional velocities of the EAC southern extension and the EAC recirculation. The poleward EAC southern extension and the equatorward EAC recirculation are synchronously strengthened (weakened) due to the local positive (negative) sea level anomalies (SLA) under geostrophic equilibrium, and the barotropic instability dominated by zonal shear is enhanced (slackened), which results in a high (low) level of EKE in the EAC region.

Changes of insular function in lifelong premature ejaculation patients before and after SSRI administration - Ming Gao; Bowen Geng; Shuming Zhang; Ke Xu; Pengyu Li; Duoli Chen; Xiao Zeng; Peng Liu; Yanzhu Wang (Psychopharmacology, 2022)

Diversity of endophytic fungi in Coptis chinensis Franch. and their activity against methicillin-resistant Staphylococcus aureus - Qianliang Ming; Xiuning Huang; Linming Guo; Dong Liu; Lingyue Qin; Yimo He; Yu Tang; Yanxia Liu; Junkang Liu; Peng Li (Folia Microbiologica, 2022)

Acute transcriptomic changes in murine RAW 264.7 cells following pseudorabies virus infection - Chao Tong; Peng-Fei Fu; Sheng-Li Ming; Lei Zeng; He-Shui Zhu; Jiang Wang (Archives of Virology, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Negative air ion exposure ameliorates depression-like behaviors induced by chronic mild stress in mice - Yun-Qing Hu; Ting-Ting Niu; Jian-ming Xu; Li Peng; Qing-Hua Sun; Ying Huang; Ji Zhou; Yu-Qiang Ding (Environmental Science and Pollution Research, 2022)
The presence of negative air ions (NAI) is suggested to be a beneficial factor in improving psychological status and used in treating depression as an alternative approach. However, more biological evidence from animal models is needed to ensure the effects of NAI on the mood regulation, through which can facilitate identification of possible underlying mechanisms. In this study, the chronic mild stress (CMS) protocol was used to induce depressive-like behaviors in mice, and the effects of NAI exposure on CMS-induced depression-like behaviors were examined. Thirty-day NAI exposure prevented the CMS-induced depression-like behaviors as shown by the restoration of sucrose preference and reduced immobility time in the tail suspension test. In addition, the elevation of serous corticosterone was present in CMS-treated mice but not existed in those with the NAI exposure. Furthermore, we observed altered ratios of some cytokines secreted by type 1 T helper (Th1) cells and Th2 cells in CMS-treated mice, but it could be restored after NAI exposure. In conclusion, NAI intervention is able to ameliorate CMS-induced depression-like behaviors in mice, and this effect is associated with the alteration of corticosterone and functional rebalance between Th1 and Th2 cells.

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Starch accumulation dynamics and transcriptome analysis of Chlorella sorokiniana during transition of sulfur nutritional status - Haiqing Xu; Jinzhi Yang; Xu Wang; Qing Peng; Yanxia Han; Xudong Liu; Kexin Liu; Shijuan Dou; Liyun Li; Guozhen Liu; Ming Yang (Frontiers in Marine Science, 2022)
Microalgae can effectively accumulate starch by using nutritional limitation methods in the context of bioalcohol fuel production. However, relatively few studies have focused on starch accumulation in microalgae and its molecular basis, especially under sulfur limitation conditions. In this study, the starch accumulation dynamics and physiological responses of Chlorella sorokiniana under sulfur starvation (SS) and sulfur replenishment (SR) conditions were investigated, and the genes involved in the transcriptional regulation were explored using RNA-seq. The starch content in C. sorokiniana cells significantly increased from 1.6% to 55.0% of dry weight within 24 h under SS conditions, and then, it decreased to 3.4% within 12 h after transition to SR conditions. However, cell growth was inhibited, and pigment content decreased under SS conditions. Using RNA-seq analysis, a total of 9720 differentially expressed genes (DEGs) induced by sulfur status were obtained. These genes were narrowed down to 454 starvation and replenishment cross-validated (SRV)-DEGs, among which 283 SRV-DEGs were significantly up-regulated and 171 SRV-DEGs were down-regulated under SS conditions, and returned to their previous state under SR conditions. The SRV-DEGs enriched in the sulfate metabolism pathway were all up-regulated under SS conditions after 6 h to speed up the sulfur metabolic cycle, and the transcriptional abundance of a sulfate transporter (SULTR4), cysteine synthase[O-acetylserine(thiol)-lyase] (OASTL), serine acetyltransferase (SAT), and methanethiol oxidase (SELENBP1) increased 8.6-fold, 12.6-fold, 8.7-fold, and 12.4-fold, respectively. Protein synthesis was correspondingly inhibited, which resulted in the reallocation of carbon and elevated the starch synthesis pathway, in which the expressions of glycogen branching enzyme (GBE) and starch synthase (SS) were up-regulated 12.0- and 3.0-fold, respectively. The fatty acid desaturase (FAD) and phosphatidic acid phosphatase (PAP) in the lipid synthesis pathway were strongly up-regulated 8.8- and 16.2-fold, respectively, indicating the competitive synthesis of lipids. The down-regulation of SRV-DEGs associated with carbon fixation, such as those in the Calvin cycle, possibly affected cell growth. The time-resolved transcriptional analysis identified the SRV-DEGs, revealing the underlying starch accumulation mechanism, as well as the relationship with cell growth and lipid synthesis.

Cunninghamia lanceolata sprout population structure, dynamics and biomass allocation changes during Phyllostachys edulis expansion in middleō-southern China - Chao Peng; Wensheng Ai; Lianghua Qi; Jia Tu; Yong Meng; Ming Yang; Meiqun Li (Trees, 2022)

Modification effects of seasonal and temperature variation on the association between exposure to nitrogen dioxide and ischemic stroke onset in Shenzhen, China - Yuchen Tian; Ming Xiang; Ji Peng; Yanran Duan; Ying Wen; Suli Huang; Lei Li; Shuyuan Yu; Jinquan Cheng; Xia Zhang; Peng Wang (International Journal of Biometeorology, 2022)

Systematic contributions of CFEM domain‐containing proteins to iron acquisition are essential for interspecies interaction of the filamentous pathogenic fungus Beauveria bassiana - Yue‐Jin Peng; Jia Hou; Hao Zhang; Jia‐Hui Lei; Hai‐Yan Lin; Jin‐Li Ding; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2022)
Summary Common in fungal extracellular membrane (CFEM) domain is unique in fungal proteins and some of which contribute to iron acquisition in yeast. However, their roles in iron acquisition remain largely unknown in filamentous fungi. In this study, 12 CFEM‐containing proteins were bioinformatically identified in the filamentous entomopathogenic fungus Beauveria bassiana , and the roles of 11 genes were genetically characterized. Transmembrane helices were critical for their association with intracellular membranes, and their number varied among proteins. Eleven CFEM genes significantly contribute to vegetative growth under iron starvation and virulence. Notably, the virulence of most disruptants could be significantly weakened by a decrease in iron availability, in which the virulence of Δ Bbcfem7 and 8 strains was partially recovered by exogenous hemin. Δ Bbcfem7 and 8 mutants displayed defective competitiveness against the sister entomopathogenic fungus Beauveria brongniartii . All 11 disruptants displayed impaired growth in the antagonistic assay with the saprotrophic fungus Aspergillus niger , which could be repressed by exogenous ferric ions. These findings not only reveal the systematic contributions of CFEM proteins to acquire two forms of iron (i.e. heme and ferric ion) in the entire lifecycle of entomopathogenic fungi but also help to better understand the mechanisms of fungus–host and inter–fungus interactions.

Natural variation MeMYB108 associated with tolerance to stress-induced leaf abscission linked to enhanced protection against reactive oxygen species in cassava - Bin Wang; Shuxia Li; Liangping Zou; Xin Guo; Jiaxin Liang; Wenbin Liao; Ming Peng (Plant Cell Reports, 2022)
Key Message Natural variation of the MeMYB108 exon was associated with reactive oxygen scavengers led to alleviate leaf abscission under drought in cassava. Abstract The reactive oxygen scavengers play important roles in regulating the cassava ( Manihot esculenta Crantz) leaf abscission induced by stresses. To date, the relationship between natural variations of MYB genes and reactive oxygen scavengers under drought in cassava genotypes remains unclear. Here, we reported the transcription factor MeMYB108 played an important role in regulating leaf abscission exposed to drought in cassava. The expression levels of MeMYB108 in abscission zones of cassava leaf pulvinus were higher in cassava genotype SC124, which were less easy to shed leaves under stress than cassava genotype SC8 when the leaf abscission induced by the same drought condition. Compared with wild type and interference expression plants, overexpression of MeMYB108 significantly reduced the drought-induced leaf abscission rate under drought. The consecutively 2-year analysis of reactive oxygen scavengers showed significant differences among different cassava genotypes under drought-induced leaf abscission, indicating the relevance between reactive oxygen scavengers and leaf abscission. Correlation analysis revealed the natural variation of the MeMYB108 exon was associated with reactive oxygen scavengers during drought-induced leaf abscission. Association analysis between pairwise LD of DNA polymorphism indicated the MeMYB108 allele enhanced the tolerance of cassava to drought-induced leaf abscission. Complementation transgenic lines containing the elite allele of MeMYB108 SC124 decreased the leaf abscission rate induced by drought conditions, demonstrating natural variation in MeMYB108 contributed to leaf abscission tolerance induced by drought in cassava. Further studies showed MeMYB108 played an active role in the tolerance of cassava to drought-induced leaf abscission by inducing scavenging of reactive oxygen species.

Chloride-binding capacity of mortars composed of marine sand subjected to external chloride penetration - Congtao Sun; Ming Sun; Tao Tao; Feng Qu; Gongxun Wang; Peng Zhang; Yantao Li; Jizhou Duan (Journal of Oceanology and Limnology, 2022)

Dioxin emission and distribution from cement kiln co-processing of hazardous solid waste - Wen-Wen Ye; Peng-Tao Cai; Ming-Xiu Zhan; Wen-Tao Jiao; Xu-Xu; Jian-Ying Fu; Tong Chen; Xiao-Dong Li (Environmental Science and Pollution Research, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Isolation and characterization of AaZFP1, a C2H2 zinc finger protein that regulates the AaIPPI1 gene involved in artemisinin biosynthesis in Artemisia annua - Yin-ai Deng; Li Li; Qian Peng; Ling-fang Feng; Jin-fen Yang; Ruo-ting Zhan; Dong-ming Ma (Planta, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Characterization and Functional Explorations of O-glycosylation Enzymes SECRET AGENT and SPINDLY in Pyrus bretschneideri - Hongru Gao; Qiuping Tan; Qionghou Li; Guodong Chen; Chao Tang; Peng Cao; Ming Qian; Mingliang Zhang; Peng Wang; Shaoling Zhang; Juyou Wu (Journal of Plant Biology, 2022)

Mechanical properties of cement soil improved using microbial-induced calcite precipitation - Shuang Li; Dong Liu; Ankit Garg; Peng Lin; Ming Huang (Arabian Journal of Geosciences, 2022)

ALKBH5 promotes the progression of infantile hemangioma through regulating the NEAT1/miR-378b/FOSL1 axis - Kun Peng; Ren-Peng Xia; Fan Zhao; Yong Xiao; Ti-Dong Ma; Ming Li; Yong Feng; Chong-Gao Zhou (Molecular and Cellular Biochemistry, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

MeSPL9 attenuates drought resistance by regulating JA signaling and protectant metabolite contents in cassava - Shuxia Li; Zhihao Cheng; Zhibo Li; Shiman Dong; Xiaoling Yu; Pingjuan Zhao; Wenbin Liao; Xiang Yu; Ming Peng (Theoretical and Applied Genetics, 2022)

Deciphering the influence of urinary microbiota on FoxP3+ regulatory T cell infiltration and prognosis in Chinese patients with non-muscle-invasive bladder cancer - Yifeng Qiu; Yubo Gao; Chunxiao Chen; Ming Xie; Pengcheng Huang; Qi Sun; Zhipeng Zhou; Biao Li; Jie Zhao; Peng Wu (Human Cell, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Integrative testing device for investigating the hydro-mechanical behavior of highly expansive clay - Yun-zhi Tan; Fan Peng; Hui Li; Hua-jun Ming; De-an Sun (Arabian Journal of Geosciences, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

Improving photosynthesis to increase grain yield potential: an analysis of maize hybrids released in different years in China - Yanyan Yan; Peng Hou; Fengying Duan; Li Niu; Tingbo Dai; Keru Wang; Ming Zhao; Shaokun Li; Wenbin Zhou (Photosynthesis Research, 2021)
In this work, we sought to understand how breeding has affected photosynthesis and to identify key photosynthetic indices that are important for increasing maize yield in the field. Our 2-year (2017–2018) field experiment used five high-yielding hybrid maize cultivars (generated in the 1970s, 2000s, and 2010s) and was conducted in the Xinjiang Autonomous Region of China. We investigated the effects of planting density on maize grain yield, photosynthetic parameters, respiration, and chlorophyll content, under three planting density regimens: 75,000, 105,000, and 135,000 plants ha −1 . Our results showed that increasing planting density to the medium level (105,000 plants ha −1 ) significantly increased grain yield (Y) up to 20.32% compared to the low level (75,000 plants ha −1 ). However, further increasing planting density to 135,000 plants ha −1 did not lead to an additional increase in yield, with some cultivars actually exhibiting an opposite trend. Interestingly, no significant changes in photosynthetic rate, dark respiration, stomatal density, and aperture were observed upon increasing planting density. Moreover, our experiments revealed a positive correlation between grain yield and the net photosynthetic rate (P n ) upon the hybrid release year. Compared to other cultivars, the higher grain yield obtained in DH618 resulted from a higher 1000-kernel weight (TKW), which can be explained by a longer photosynthetic duration, a higher chlorophyll content, and a lower ratio of chlorophyll a / b . Moreover, we found that a higher leaf area per plant and the leaf area index (HI) do not necessarily result in an improvement in maize yield. Taken together, we demonstrated that higher photosynthetic capacity, longer photosynthetic duration, suitable LAI, and higher chlorophyll content with lower chlorophyll a / b ratio are important factors for obtaining high-yielding maize cultivars and can be used for the improvement of maize crop yield.

Terpenoids with neurotrophic and anti-neuroinflammatory activities from the cultures of the fungus Cyathus stercoreus - Xia Yin; Jianzhao Qi; Yixiao Li; Ze’an Bao; Peng Du; Rongwei Kou; Weiwei Wang; Jin-Ming Gao (Natural Product Research, 2021)

Identification of a recessive gene YrZ15-1370 conferring adult plant resistance to stripe rust in wheat-Triticum boeoticum introgression line - Minghu Zhang; Xin Liu; Ting Peng; Dinghao Wang; Dongyu Liang; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Theoretical and Applied Genetics, 2021)

White matter characteristics between amygdala and prefrontal cortex underlie depressive tendency in end stage renal disease patients before the dialysis initiation - Junya Mu; Liang Ma; Dun Ding; Xueying Ma; Peng Li; Ruixiao Li; Ming Zhang; Jixin Liu (Brain Imaging and Behavior, 2021)

Flexible reconfiguration of functional brain networks as a potential neural mechanism of creativity - Junchao Li; Natasza Orlov; Zengjian Wang; Bingqing Jiao; Yibo Wang; Huawei Xu; Hui Yang; Yingying Huang; Yan Sun; Peng Zhang; Rengui Yu; Ming Liu; et al. (Brain Imaging and Behavior, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

DREAM - Zhu-Qing Gong; Peng Gao; Chao Jiang; Xiu-Xia Xing; Hao-Ming Dong; Tonya White; F. Xavier Castellanos; Hai-Fang Li; Xi-Nian Zuo (Neuroinformatics, 2021)
Rhythms of the brain are generated by neural oscillations across multiple frequencies. These oscillations can be decomposed into distinct frequency intervals associated with specific physiological processes. In practice, the number and ranges of decodable frequency intervals are determined by sampling parameters, often ignored by researchers. To improve the situation, we report on an open toolbox with a graphical user interface for decoding rhythms of the brain system (DREAM). We provide worked examples of DREAM to investigate frequency-specific performance of both neural (spontaneous brain activity) and neurobehavioral (in-scanner head motion) oscillations. DREAM decoded the head motion oscillations and uncovered that younger children moved their heads more than older children across all five frequency intervals whereas boys moved more than girls in the age of 7 to 9 years. It is interesting that the higher frequency bands contain more head movements, and showed stronger age-motion associations but weaker sex-motion interactions. Using data from the Human Connectome Project, DREAM mapped the amplitude of these neural oscillations into multiple frequency bands and evaluated their test-retest reliability. The resting-state brain ranks its spontaneous oscillation’s amplitudes spatially from high in ventral-temporal areas to low in ventral-occipital areas when the frequency band increased from low to high, while those in part of parietal and ventral frontal regions are reversed. The higher frequency bands exhibited more reliable amplitude measurements, implying more inter-individual variability of the amplitudes for the higher frequency bands. In summary, DREAM adds a reliable and valid tool to mapping human brain function from a multiple-frequency window into brain waves.

Mining subsidence prediction for multi-seam and non-rectangular goafs based on probability integral model: a case study from China - Shuaiying Peng; Shengwu Qin; Ming Wang; Guangjie Li (Arabian Journal of Geosciences, 2021)

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

miR-34c inhibits PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway - Wei-feng Wan; Xin Zhang; Chang-ren Huang; Li-gang Chen; Xiao-bo Yang; Kun-yang Bao; Tang-ming Peng (Molecular Biology Reports, 2021)
The purpose of this study was to explore the effect of miR-34c on PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway, so as to find a new method for early diagnosis and treatment of cardiovascular disease. HA-VSMCs were treated with platelet-derived growth factor-BB (PDGF-BB) at 0 h, 12 h, 24 h, 48 h or 36 h to explore the optimal time for phenotypic transformation of VSMCs. And then, PDGF-BB-induced HA-VSMCs were transfected with miR-34c mimics/mimics NC and pcDNA3.1-PDGFR-β/pcDNA3.1-NC to observe cell biological behaviour. CCK8 was used to detect cell proliferation activity. Transwell chamber assay was used to detect cell invasion. Early apoptosis was analyzed by flow cytometry. The expression of α-SMA and Smemb was detected by immunofluorescence staining. The expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 were analyzed by Western blot analysis. The expression of miR-34a, miR-34b and miR-34c was detected by RT-PCR, and the targeting relationship between miR-34c and PDGFR-β was detected by luciferase reporting assay. The results indicated the proliferation and migration of PDGF-BB-induced HA-VSMCs significantly increased, and apoptosis significantly decreased. Besides, α-SMA decreased significantly, while Smemb increased significantly. Furthermore, expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 increased significantly, and SIRT1 decreased significantly. Experimental results showed that, miR-34c mimics significantly inhibited cell proliferation and migration, and promoted cell apoptosis, and miR-34c inhibitor had the opposite effects. MiR-34c mimics significantly increased α-SMA expression and decreased Smemb expression, while the opposite effects were reflected after transfection with miR-34c inhibitor. Moreover, miR-34c mimics significantly decreased the expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1, and significantly increased the expression of SIRT1, while miR-34c inhibitor had the opposite effects. Luciferase assay confirmed that PDGFR-β was a potential target of miR-34c. Subsequently, PDGF-BB-induced HA-VSMCs were co-transfected with miR-34c mimics and pcDNA3.1-PDGFR-β. The results indicated that PDGFR-β reversed the biological function of miR-34c mimic. The results revealed the potential application value of miR-34c as a marker molecule of phenotypic transformation, providing a potential target for improving phenotypic transformation.

Vegetation dynamics and climate variability over the past 2000 years inferred from Son Kul marsh in the western Tianshan Mountains - Dong-liang Zhang; Yao-ming Li; Kai-hui Li; Xue-xi Ma; Yun-peng Yang (Journal of Mountain Science, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Effects of biochar properties on the bioremediation of the petroleum-contaminated soil from a shale-gas field - Hong-Yang Ren; Zi-Jing Wei; Yan Wang; Yuan-Peng Deng; Ming-Yu Li; Bing Wang (Environmental Science and Pollution Research, 2020)

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Sauchinone: a prospective therapeutic agent-mediated EIF4EBP1 down-regulation suppresses proliferation, invasion and migration of lung adenocarcinoma cells - Sheng-Qian Li; Jing Feng; Ming Yang; Xiao-Peng Ai; Mei He; Fu Liu (Journal of Natural Medicines, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

Long noncoding RNA LINC00520 accelerates the progression of colorectal cancer by serving as a competing endogenous RNA of microRNA-577 to increase HSP27 expression - Xi-Han Jin; Yong-Gang Hong; Peng Li; Li-Qiang Hao; Ming Chen (Human Cell, 2020)

Identification of drug resistance genes and drug resistance analysis of Salmonella in the duck farm environment of Zhanjiang, China - Jin-Li Niu; Jin-Ju Peng; Yue-Yue Ming; Qi-Chao Ma; Wen-Chao Liu; Yi Ma (Environmental Science and Pollution Research, 2020)

Host functional and phylogenetic composition rather than host diversity structure plant–herbivore networks - Ming‐Qiang Wang; Yi Li; Douglas Chesters; Helge Bruelheide; Keping Ma; Peng‐Fei Guo; Qing‐Song Zhou; Michael Staab; Chao‐Dong Zhu; Andreas Schuldt (Molecular Ecology, 2020)
Declining plant diversity alters ecological networks, such as plant–herbivore interactions. However, our knowledge of the potential mechanisms underlying effects of plant species loss on plant–herbivore network structure is still limited. We used DNA barcoding to identify herbivore–host plant associations along declining levels of tree diversity in a large‐scale, subtropical biodiversity experiment. We tested for effects of tree species richness, host functional and phylogenetic diversity, and host functional (leaf trait) and phylogenetic composition on species, phylogenetic and network composition of herbivore communities. We found that phylogenetic host composition and related palatability/defence traits but not tree species richness significantly affected herbivore communities and interaction network complexity at both the species and community levels. Our study indicates that evolutionary dependencies and functional traits of host plants determine the composition of higher trophic levels and corresponding interaction networks in species‐rich ecosystems. Our findings highlight that characteristics of the species lost have effects on ecosystem structure and functioning across trophic levels that cannot be predicted from mere reductions in species richness.

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Molecular cloning and expression analysis of myd88 from oriental weatherfish ( Misgurnus anguillicaudatus ) in response to bacterial challenge - Jian H. Chen; Xue Li; Meng J. Wang; Chun M. Wang; Yan Q. Peng; Hai H. Wang; Ming Zhu (Journal of Fish Biology, 2020)
Myeloid differentiation factor 88 (Myd88) plays an important role in both innate and adaptive immune response. In this study, the full‐length complementary DNA (cDNA) of myd88 from Misgurnus anguillicaudatus was characterized. The myd88 cDNA is 1333 bp in length and contains an 855 bp open reading frame encoding a predicted protein of 284 amino acids. The predicted protein possesses typical Myd88 domain structural features including a death domain in the N‐terminus, and box 1, 2, and 3 motifs of the Toll/IL‐1 receptor domain in the C‐terminus. Quantitative real‐time PCR (qRT‐PCR) revealed that myd88 messenger RNA (mRNA) was ubiquitously expressed in all examined tissues, especially highly in brain, kidney, blood, intestines and liver. qRT‐PCR and western blotting were used to determine the mRNA and protein levels of Myd88 after Aeromonas veronii challenge, respectively. The Myd88 was remarkably upregulated in response to infection of A. veronii. These results suggested that Myd88 may play a vital role during the immune response of M. anguillicaudatus against bacterial infection.

Two new xanthone glycosides from Swertia punicea Hemsl. and their anti-inflammatory activity - Lin-Yun Mou; Hai-Yan Wu; En-Guang Ma; Ming-Feng Wang; Yan-Qing Duan; Sheng Lei; Gan-Peng Li (Natural Product Research, 2020)

Quantifying irrigation cooling benefits to maize yield in the US Midwest - Yan Li; Kaiyu Guan; Bin Peng; Trenton E. Franz; Brian Wardlow; Ming Pan (Global Change Biology, 2020)
Irrigation is an important adaptation strategy to improve crop resilience to global climate change. Irrigation plays an essential role in sustaining crop production in water‐limited regions, as irrigation water not only benefits crops through fulfilling crops' water demand but also creates an evaporative cooling that mitigates crop heat stress. Here we use satellite remote sensing and maize yield data in the state of Nebraska, USA, combined with statistical models, to quantify the contribution of cooling and water supply to the yield benefits due to irrigation. Results show that irrigation leads to a considerable cooling on daytime land surface temperature (−1.63°C in July), an increase in enhanced vegetation index (+0.10 in July), and 81% higher maize yields compared to rainfed maize. These irrigation effects vary along the spatial and temporal gradients of precipitation and temperature, with a greater effect in dry and hot conditions, and decline toward wet and cool conditions. We find that 16% of irrigation yield increase is due to irrigation cooling, while the rest (84%) is due to water supply and other factors. The irrigation cooling effect is also observed on air temperature (−0.38 to −0.53°C) from paired flux sites in Nebraska. This study highlights the non‐negligible contribution of irrigation cooling to the yield benefits of irrigation, and such an effect may become more important in the future with continued warming and more frequent droughts.

Tide-Surge Interaction in the Pearl River Estuary: A Case Study of Typhoon Hato - Peng Zheng; Ming Li; Caixia Wang; Judith Wolf; Xueen Chen; Michela De Dominicis; Peng Yao; Zhan Hu (Frontiers in Marine Science, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Involvement of the JNK signaling in granular corneal dystrophy by modulating TGF-β-induced TGFBI expression and corneal fibroblast apoptosis - Danyao Nie; Xinhua Liu; Yuan Wang; Wenling He; Ming Li; Yun Peng; Jing Zhang; Liangnan Sun; Zonghui Yan; Lin Ye (In Vitro Cellular & Developmental Biology - Animal, 2020)

The variation of motor-related brain structure and its relation to abnormal motor behaviors in end-stage renal disease patients with restless legs syndrome - Junya Mu; Xiaohui Liu; Shaohui Ma; Tao Chen; Xueying Ma; Peng Li; Dun Ding; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2020)

Pelagivirga dicentrarchi sp. nov., a member of the family Rhodobacteraceae isolated from the gut microflora of sea bass (Dicentrarchus labrax L.) - Chang-Ming Li; Xin-Peng Wang; Liu-Yan Zhou; Guan-Jun Chen; Zong-Jun Du (Antonie van Leeuwenhoek, 2020)

Effect of Dietary Selenium Supplementation on Growth and Reproduction of Silkworm Bombyx mori L. - Li Jiang; Li-Li Peng; Yu-Yao Cao; Kiran Thakur; Fei Hu; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2020)

Water and heat availability are drivers of the aboveground plant carbon accumulation rate in alpine grasslands on the Tibetan Plateau - Jian Sun; Tian‐Cai Zhou; Miao Liu; You‐Chao Chen; Guo‐Hua Liu; Ming Xu; Pei‐Li Shi; Fei Peng; Atsushi Tsunekawa; Yu Liu; Xiao‐Dan Wang; Shi‐Kui Dong; et al. (Global Ecology and Biogeography, 2020)
Aim Climate change is expected to have important effects on plant phenology and carbon storage, with further shifts predicted in the future. Therefore, we proposed the community carbon accumulation rate (CAR) from the start of the growing season (SOS) to the peak of the growing season (POS) to fill the gap that the dynamic interactions between plant phenology and plant carbon research. Location Tibetan Plateau. Major taxa Alpine grassland plants. Time period 2015. Methods We conducted a transect survey across grasslands to measure community aboveground net primary production and carbon concentration. Additionally, phenology indicator data (SOS and POS) were extracted from the Global Inventory Modeling and Mapping Studies (GIMMS) normalized difference vegetation index version 3 database. Next, we used ‘ changepoint ’ analysis to detect the patterns of CARs, and performed linear regression and one‐way ANOVA to explore the variability of CARs in response to the environmental factors. Ultimately, the total effects of environmental factors on CARs were illustrated by a structural equation model. Results Our results indicated that three CAR patterns were detected, which are low‐CAR (0.15 g/m 2 /day), medium‐CAR (0.31 g/m 2 /day) and high‐CAR (0.84 g/m 2 /day) patterns. We found that the availabilities of water and heat mediated CARs by regulating soil nutrition variability, and that drought climate and insufficient soil resources co‐constrained the community CAR at long time‐scales. In contrast, high CAR could be explained by more water and heat availability via either direct or indirect effects on soil moisture and soil nutrients. Main conclusions Our findings highlight that water and heat availability are critical driving factors in ecological carbon accumulation processes undergoing climate change. Meanwhile, the vegetative phenology also has important effect on carbon accumulation. Consequently, we propose incorporating the dynamic interactions between plant phenology and plant carbon into the ecological carbon cycle model to improve our understanding of resource utilization and survival strategies of plants under environmental change.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Molecular identification and phylogenetic relationships of clinical Nocardia isolates - Ming Wei; Peng Wang; Chunxia Yang; Li Gu (Antonie van Leeuwenhoek, 2019)

Reduced redox‐dependent mechanism and glucose‐mediated reversal in gentamicin‐resistant Vibrio alginolyticus - Song Zhang; Jie Wang; Ming Jiang; Di Xu; Bo Peng; Xuan‐xian Peng; Hui Li (Environmental Microbiology, 2019)
Summary Strategy of managing antibiotic‐resistant Vibrio alginolyticus , a bacterial pathogen that threatens human health and animal farming, is not available due to the lack of knowledge about the underlying mechanism of antibiotic resistance. Here, we showed that gentamicin‐resistant V . alginolyticus (VA‐R GEN ) has four mutations on metabolism and one mutation on a two‐component system by whole‐genome and PCR‐based sequencing, indicating the metabolic shift in VA‐R GEN. Thus, metabolic profile was investigated by GC–MS based metabolomics. Glucose was identified as a crucial biomarker, whose abundance was decreased in VA‐R GEN . Further analysis with iPath, and gene expression and enzyme activity of the pyruvate cycle (the P cycle) demonstrated a global depressed metabolic pathway network in VA‐R GEN . Consistently, NADH, sodium‐pumping NADH:ubiquinone oxidoreductase (Na(+)‐NQR) system, membrane potential and intracellular gentamicin were decreased in VA‐R GEN . These findings indicate that the reduced redox state contributes to antibiotic resistance. Interestingly, exogenous glucose potentiated gentamicin to efficiently kill VA‐R GEN through the promotion of the P cycle, NADH, membrane potential and intracellular gentamicin. The potentiation was further confirmed in a zebrafish model. These results indicate that the gentamicin resistance reduces the P cycle and Na(+)‐NQR system and thereby decreases redox state, membrane potential and gentamicin uptake, which can be reversed by exogenous glucose.

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

Assessing the influence of the minimum measured diameter on forest spatial patterns and nearest neighborhood relationships - Yuan-fa Li; Hai-peng Yang; Hong-xiang Wang; Shao-ming Ye; Wen-zhen Liu (Journal of Mountain Science, 2019)

Study on forward and inversion modeling of array laterolog logging in a horizontal/highly deviated well - Peng Zhu; Zhiqiang Li; Ming Chen; Yixin Dong (Acta Geophysica, 2019)

Multiparameter least-squares reverse time migration for acoustic—elastic coupling media based on ocean bottom cable data - Ying-Ming Qu; Chong-Peng Huang; Chang Liu; Chang Zhou; Zhen-Chun Li; Qurmet Worral (Applied Geophysics, 2019)

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB - Peng Zou; Hong-Ming Ji; Jian-Wei Zhao; Xin-Min Ding; Zi-Gang Zhen; Xuan Zhang; Xiao-Qi Nie; Li-Xiong Xue (Inflammopharmacology, 2019)

The Characteristics and Distribution of Eukaryotic Phytoplankton Community in Liaodong Bay, China - Lun Song; Jing Wu; Jing Du; Nan Li; GuangJun Song; Kun Wang; Ming Sun; Peng Wang (Ocean Science Journal, 2019)

Mechanism underlying 2n male and female gamete formation in lemon via cytological and molecular marker analysis - Kai-Dong Xie; Qiang-Ming Xia; Jun Peng; Xiao-Meng Wu; Zong-Zhou Xie; Chun-Li Chen; Wen-Wu Guo (Plant Biotechnology Reports, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Quantitative evaluation of low-permeability gas reservoirs based on an improved fuzzy-gray method - Peng Zhu; Zhaoqun Zhu; Yuanyuan Zhang; Lianpu Sun; Yixin Dong; Zhiqiang Li; Ming Chen (Arabian Journal of Geosciences, 2019)

Application Research on Gob-Side Entry Retaining Methods in No. 1200 Working Face in Zhongxing Mine - Sun Xiao-ming; Li Gan; Song Peng; Miao Chengyu; Zhao Chengwei; Li Qi; Xia Xing (Geotechnical and Geological Engineering, 2019)

Adsorption characteristics of Cu(II) and Zn(II) by nano-alumina material synthesized by the sol-gel method in batch mode - Ren-yu Wang; Wei Zhang; Li-ying Zhang; Tian Hua; Gang Tang; Xiao-qian Peng; Ming-hui Hao; Qi-ting Zuo (Environmental Science and Pollution Research, 2019)

An invasive population of Solidago canadensis is less sensitive to warming and nitrogen-addition than its native population in an invaded range - Yang Peng; Jian-Xia Yang; Xiao-Hui Zhou; Pei-Hao Peng; Jing-Ji Li; Shu-Min Zhang; Wei-Ming He (Biological Invasions, 2019)

sEMG Based Gait Phase Recognition for Children with Spastic Cerebral Palsy - Peng-na Wei; Rongfu Xie; Rongnian Tang; Chuang Li; Janis Kim; Ming Wu (Annals of Biomedical Engineering, 2019)

A new regulator RsdA mediating fungal secondary metabolism has a detrimental impact on asexual development in Pestalotiopsis fici - Shuang Zhou; Peng Zhang; Haichuan Zhou; Xingzhong Liu; Shu‐Ming Li; Liangdong Guo; Kuan Li; Wen‐Bing Yin (Environmental Microbiology, 2019)
Summary Secondary metabolite (SM) production and development are correlated processes in fungi that are often coordinated by pleiotropic regulators. The eukaryotic regulators are critical players in mediating SM production related to fungal development, yet little data are available to support this hypothesis. In this study, a global regulator, RsdA ( r egulation of s econdary metabolism and d evelopment), was identified through genome‐wide analysis and deletion of the regulator gene in the endophytic fungus Pestalotiopsis fici . Here, we established that RsdA regulation of SMs is accompanied by the repression of asexual development. Deletion of rsdA significantly reduces not only asexual development, resulting in low sporulation and abnormal conidia, but also the major SM production, while remarkably increasing the melanin production. Overproduction of melanin leads to the formation of unusual, heavily pigmented hyphae. Transcriptome analysis data provide the evidence that RsdA globally regulates genes involved in secondary metabolism and asexual development. Double deletion of rsdA and the melanin polyketide synthase gene PfmaE confirm that RsdA regulation of asexual development is independent of the melanin biosynthetic pathway. Finally, our results demonstrate that RsdA can be used for the discovery of secondary metabolites in filamentous fungi.

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Altered intrinsic brain activity and memory performance improvement in patients with end-stage renal disease during a single dialysis session - Peng Li; Dun Ding; Xue-ying Ma; Hua-wen Zhang; Ji-xin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Evaluating the suitability of different terrains for sustaining human settlements according to the local elevation range in China using the ASTER GDEM - Chi-wei Xiao; Zhi-ming Feng; Peng Li; Zhen You; Jia-kun Teng (Journal of Mountain Science, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Boron Affects the Development of the Kidney Through Modulation of Apoptosis, Antioxidant Capacity, and Nrf2 Pathway in the African Ostrich Chicks - Haseeb Khaliq; Wang Jing; Xiao Ke; Yang Ke-Li; Sun Peng-peng; Lei Cui; Qiu Wei-wei; Lei Zhixin; Liu Hua-Zhen; Song Hui; Zhong Ju-Ming; Peng Ke-Mei (Biological Trace Element Research, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Association between abnormal thalamic metabolites and sleep disturbance in patients with end-stage renal disease - Xueying Ma; Yan Zhang; Shaohui Ma; Peng Li; Dun Ding; Hua Liu; Jixin Liu; Ming Zhang (Metabolic Brain Disease, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

The relationship between putamen-SMA functional connectivity and sensorimotor abnormality in ESRD patients - Dun Ding; Peng Li; Xue-ying Ma; Wang-huan Dun; Shi-feng Yang; Shao-hui Ma; Hong-juan Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

Autophagy‐related gene BbATG11 is indispensable for pexophagy and mitophagy, and contributes to stress response, conidiation and virulence in the insect mycopathogen Beauveria bassiana - Jin‐Li Ding; Yue‐Jin Peng; Xin‐Ling Chu; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2018)
Summary Autophagy is a conserved degradation system in eukaryotic cells that includes non‐selective and selective processes. Selective autophagy functions as a selective degradation mechanism for specific substrates in which autophagy‐related protein 11 (ATG11) acts as an essential scaffold protein. In B. bassiana , there is a unique ATG11 family protein, which is designated as BbATG11 . Disruption of BbATG11 resulted in significantly reduced conidial germination under starvation stress. The mutant Δ BbATG11 displayed enhanced sensitivity to oxidative stress and impaired asexual reproduction. The conidial yield was reduced by approximately 75%, and this defective phenotype could be repressed by increasing exogenous nutrients. The virulence of the Δ BbATG11 mutant strain was significantly impaired as indicated in topical and intra‐hemocoel injection bioassays, with a greater reduction in topical infection. Notably, BbATG11 was involved in pexophagy and mitophagy, but these two autophagic processes appeared in different fungal physiological aspects. Both pexophagy and mitophagy were associated with nutrient shift, starvation stress and growth in the host hemocoel, but only pexophagy appeared in both oxidation‐stressed cells and aerial mycelia. This study highlights that BbATG11 mediates pexophagy and mitophagy in B. bassiana and links selective autophagy to the fungal stress response, conidiation and virulence.

Abnormal interaction between cognitive control network and affective network in patients with end-stage renal disease - Junya Mu; Tao Chen; Qianqian Liu; Dun Ding; Xueying Ma; Peng Li; Anmao Li; Mingxia Huang; Zengjun Zhang; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Re-delineating mountainous areas with three topographic parameters in Mainland Southeast Asia using ASTER global digital elevation model data - Chi-wei Xiao; Peng Li; Zhi-ming Feng (Journal of Mountain Science, 2018)

An improved grey wolf optimizer algorithm for the inversion of geoelectrical data - Si-Yu Li; Shu-Ming Wang; Peng-Fei Wang; Xiao-Lu Su; Xin-Song Zhang; Zhi-Hui Dong (Acta Geophysica, 2018)

Physiological and quantitative proteomic analyses unraveling potassium deficiency stress response in alligator weed (Alternanthera philoxeroides L.) root - Li-qin Li; Lun Liu; Wei Zhuo; Qian Chen; Sheng Hu; Shuang Peng; Xi-yao Wang; Yi-fei Lu; Li-ming Lu (Plant Molecular Biology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Optimized staggered-grid finite-difference operators using window functions - Ying-Jun Ren; Jian-Ping Huang; Peng Yong; Meng-Li Liu; Chao Cui; Ming-Wei Yang (Applied Geophysics, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Re–Os dating of molybdenite and in-situ Pb isotopes of sulfides from the Lamo Zn–Cu deposit in the Dachang tin-polymetallic ore field, Guangxi, China - Hai Zhao; Wenchao Su; Peng Xie; Nengping Shen; Jiali Cai; Ming Luo; Jie Li; Zhian Bao (Acta Geochimica, 2018)

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Magnetic nanoparticles based cancer therapy: current status and applications - Huan Zhang; Xiao Li Liu; Yi Fan Zhang; Fei Gao; Ga Long Li; Yuan He; Ming Li Peng; Hai Ming Fan (Science China Life Sciences, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Effects of Boron Supplementation on Expression of Hsp70 in the Spleen of African Ostrich - Khaliq Haseeb; Jing Wang; Ke Xiao; Ke-li Yang; Peng-peng Sun; Xing-tong Wu; You Luo; Hui Song; Hua-zhen Liu; Ju-ming Zhong; Ke-mei Peng (Biological Trace Element Research, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Rice straw decomposition affects diversity and dynamics of soil fungal community, but not bacteria - Peng Li; Yongchun Li; Xianqing Zheng; Lina Ding; Feng Ming; Aihu Pan; Weiguang Lv; Xueming Tang (Journal of Soils and Sediments, 2018)

RETRACTED ARTICLE: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2018)

A risk management system for meteorological disasters of solar greenhouse vegetables - Ming Li; Sining Chen; Fang Liu; Li Zhao; Qingyu Xue; Hui Wang; Meixiang Chen; Peng Lei; Dongmei Wen; Jorge Antonio Sanchez-Molina; Jose Fernando Bienvenido; Zhenfa Li; et al. (Precision Agriculture, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Comparative proteomics analysis of young spikes of wheat in response to Fusarium graminearum infection - Lina Ding; Ming Li; Peng Li; Jun Cao (Acta Physiologiae Plantarum, 2017)

Neuronal nitric oxide synthase modulation of intracellular Ca2+ handling overrides fatty acid potentiation of cardiac inotropy in hypertensive rats - Chun Li Jin; Ming Zhe Yin; Jin Chul Paeng; Seunggyun Ha; Jeong Hoon Lee; Peng Jin; Chun Zi Jin; Zai Hao Zhao; Yue Wang; Keon Wook Kang; Chae Hun Leem; Jong-Wan Park; et al. (Pflügers Archiv - European Journal of Physiology, 2017)

Transcriptomic insights into the alternative splicing‐mediated adaptation of the entomopathogenic fungus Beauveria bassiana to host niches: autophagy‐related gene 8 as an example - Wei‐Xia Dong; Jin‐Li Ding; Yang Gao; Yue‐Jin Peng; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2017)
Summary Alternative splicing (AS) regulates various biological processes in fungi by extending the cellular proteome. However, comprehensive studies investigating AS in entomopathogenic fungi are lacking. Based on transcriptome data obtained via dual RNA‐seq, the first overview of AS events was developed for Beauveria bassiana growing in an insect haemocoel. The AS was demonstrated for 556 of 8840 expressed genes, accounting for 5.4% of the total genes in B. bassiana . Intron retention was the most abundant type of AS, accounting for 87.1% of all splicing events and exon skipping events were rare, only accounting for 2.0% of all events. Functional distribution analysis indicated an association between alternatively spliced genes and several physiological processes. Notably, B. bassiana autophagy‐related gene 8 ( BbATG8 ), an indispensable gene for autophagy, was spliced at an alternative 5′ splice site to generate two transcripts ( BbATG8‐α and BbATG8‐β ). The BbATG8‐α transcript was necessary for fungal autophagy and oxidation tolerance, while the BbATG8‐β transcript was not. These two transcripts differentially contributed to the formation of conidia or blastospores as well as fungal virulence. Thus, AS acts as a powerful post‐transcriptional regulatory strategy in insect mycopathogens and significantly mediates fungal transcriptional adaption to host niches.

Identification of a Bipolar Disorder Vulnerable Gene CHDH at 3p21.1 - Hong Chang; Lingyi Li; Tao Peng; Maria Grigoroiu-Serbanescu; Sarah E. Bergen; Mikael Landén; Christina M. Hultman; Andreas J. Forstner; Jana Strohmaier; Julian Hecker; Thomas G. Schulze; Bertram Müller-Myhsok; et al. (Molecular Neurobiology, 2017)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Prenylated benzoic acid derivatives from the stem of Euodia lepta - Ming-Bo Zhao; Si-Xiang Zhou; Qing-Ying Zhang; Wei-Feng Wei; Ming-Hui Li; Jian-Yong Xing; Yong Jiang; Peng-Fei Tu (Natural Product Research, 2017)

Geochemistry and geochronology of the mafic dikes in the Taipusi area, northern margin of North China Craton: Implications for Silurian tectonic evolution of the Central Asian Orogen - Jing-Hua Wu; Huan Li; Xiao-Shuang Xi; Hua Kong; Qian-Hong Wu; Neng-Li Peng; Xi-Ming Wu; Jing-Ya Cao; Jillian Aira S Gabo-Ratio (Journal of Earth System Science, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

CRISPR/Cas9-mediated gene editing in human zygotes using Cas9 protein - Lichun Tang; Yanting Zeng; Hongzi Du; Mengmeng Gong; Jin Peng; Buxi Zhang; Ming Lei; Fang Zhao; Weihua Wang; Xiaowei Li; Jianqiao Liu (Molecular Genetics and Genomics, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

The formation of porphyry copper deposits - Weidong Sun; Jin-tuan Wang; Li-peng Zhang; Chan-chan Zhang; He Li; Ming-xing Ling; Xing Ding; Cong-ying Li; Hua-ying Liang (Acta Geochimica, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Impact of genetic polymorphisms related to clopidogrel or acetylsalicylic acid pharmacology on clinical outcome in Chinese patients with symptomatic extracranial or intracranial stenosis - Zhigang Zhao; Xingang Li; Shusen Sun; Shenghui Mei; Ning Ma; Zhongrong Miao; Ming Zhao; Shiqi Peng (European Journal of Clinical Pharmacology, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

3D finite-difference modeling algorithm and anomaly features of ZTEM - Tao Wang; Han-Dong Tan; Zhi-Qiang Li; Kun-Peng Wang; Zhi-Ming Hu; Xing-Dong Zhang (Applied Geophysics, 2016)

Xanthones from the herb of Swertia elata and their anti-TMV activity - Wei Jiang; Dong-Lai Zhu; Ming-Feng Wang; Qing-Song Yang; Ma-Yi Zuo; Liang Zeng; Gan-Peng Li (Natural Product Research, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Effects of climate change on potential habitats of the cold temperate coniferous forest in Yunnan province, southwestern China - Wang-jun Li; Ming-chun Peng; Motoki Higa; Nobuyuki Tanaka; Tetsuya Matsui; Cindy Q. Tang; Xiao-kun Ou; Rui-wu Zhou; Chong-yun Wang; Hai-zhong Yan (Journal of Mountain Science, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

A new flavone C -glycoside and a new bibenzyl from Bulbophyllum retusiusculum - Ming-Hui Yang; Yun-Shan Fang; Le Cai; Ying Li; Jian-Wei Dong; Tian-Peng Yin; Cai-Li Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Silicon nutrition alleviates the lipid peroxidation and ion imbalance of Glycyrrhiza uralensis seedlings under salt stress - Yue-Tong Li; Wen-Jin Zhang; Jia-Jia Cui; Duo-Yong Lang; Ming Li; Qi-Peng Zhao; Xin-Hui Zhang (Acta Physiologiae Plantarum, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Prediction of drug-induced eosinophilia adverse effect by using SVM and naïve Bayesian approaches - Hui Zhang; Peng Yu; Ming-Li Xiang; Xi-Bo Li; Wei-Bao Kong; Jun-Yi Ma; Jun-Long Wang; Jin-Ping Zhang; Ji Zhang (Medical & Biological Engineering & Computing, 2016)

Using interval maxima regression (IMR) to determine environmental optima controlling Microcystis spp. growth in Lake Taihu - Ming Li; Qiang Peng; Man Xiao (Environmental Science and Pollution Research, 2016)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Association between NCF4 rs4821544T/C polymorphism and inflammatory bowel disease risk in Caucasian: a meta-analysis - Peng-Bo Wu; Jin-Fen Dai; Qian Wang; Guo Zhang; Shi-Yun Tan; Ming Li; Hui-Lan Ye (Inflammation Research, 2015)

Effect of negative pressure on growth, secretion and biofilm formation of Staphylococcus aureus - Tongtong Li; Guoqi Wang; Peng Yin; Zhirui Li; Licheng Zhang; Jianheng Liu; Ming Li; Lihai Zhang; Li Han; Peifu Tang (Antonie van Leeuwenhoek, 2015)

Bioavailability of sedimentary phosphorus under repeated sediment resuspension with the addition of algae - Wu Xiao-Fei; Li Da-Peng; Wang Ming; Wang Ren (Environmental Science and Pollution Research, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

NCoR negatively regulates adipogenic differentiation of mesenchymal stem cells - Gao Hong-Wei; Liu Lan; Xing De-Guo; Liu Zhong-Hao; Ren Peng; Li Zhi-Qiang; Shan Guo-Qiang; Gong Ming-Zhi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Large deformation failure analysis of the soil slope based on the material point method - Peng Huang; Shun-li Li; Hu Guo; Zhi-ming Hao (Computational Geosciences, 2015)

A Time-Course Proteomic Analysis of Rice Triggered by Plant Activator BTH - Zhuo Chen; Binghua Chen; Qin Guo; Li Shi; Ming He; Zhiyang Qin; Lianhua Li; Peng He; Zhenchao Wang; Deyu Hu; Song Yang (Journal of Plant Growth Regulation, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Analyzing the impact of urbanization on energy consumption in Jiangsu Province - Ming Zhang; Peng Li (Natural Hazards, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Synthesis and in vitro antiproliferative activity of novel benzisoselenazolone derivatives - Li-na Xuan; Peng Wang; Kai Zhang; Yan-ping Shi; Yu-ming Liu; Tao Zhu; Bao-quan Chen (Medicinal Chemistry Research, 2015)

Comparative genomic sequence analysis of Chinese orf virus strain NA1/11 with other parapoxviruses - Wei Li; Wenbo Hao; Yongzheng Peng; Chaohui Duan; Chengbi Tong; Deguang Song; Feng Gao; Ming Li; Daniel L. Rock; Shuhong Luo (Archives of Virology, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

Dystrophin Involved in the Susceptibility of Slow Muscles to Hindlimb Unloading via Concomitant Activation of TGF-β1/Smad3 Signaling and Ubiquitin–Proteasome Degradation in Mice - Peng Zhang; Wenjiong Li; Hongju Liu; Jinglong Li; Jing Wang; Yanan Li; Xiaoping Chen; Zhong Yang; Ming Fan (Cell Biochemistry and Biophysics, 2014)

Electroacupuncture Attenuates Reference Memory Impairment Associated with Astrocytic NDRG2 Suppression in APP/PS1 Transgenic Mice - Feng Wang; Haixing Zhong; Xuying Li; Ye Peng; Renee Kinden; Wei Liang; Xin Li; Ming Shi; Lixin Liu; Qiang Wang; Lize Xiong (Molecular Neurobiology, 2014)

Plasmid-encoding vasostatin inhibited the growth and metastasis of human hepatocellular carcinoma cells - Xing-chen Peng; Ming Wang; Xu-xia Chen; Jing Liu; Gui-hua Xiao; Hong-li Liao (Molecular and Cellular Biochemistry, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

Individual and joint toxic effects of cadmium sulfate and α-naphthoflavone on the development of zebrafish embryo - Jian Yin; Jian-ming Yang; Feng Zhang; Peng Miao; Ying Lin; Ming-li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Short-term effects of meteorological factors on children hand, foot and mouth disease in Guangzhou, China - Chun Chen; Hualiang Lin; Xiaoquan Li; Lingling Lang; Xincai Xiao; Peng Ding; Peng He; Ying Zhang; Ming Wang; Qiyong Liu (International Journal of Biometeorology, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System - Fengxia Guo; Xiaohong Li; Juan Peng; Yaling Tang; Qin Yang; Lushan Liu; Zuo Wang; Zhisheng Jiang; Ming Xiao; Chuyu Ni; Ruixing Chen; Dangheng Wei; et al. (Annals of Biomedical Engineering, 2014)

Accumulated Deformation Behavior and Computational Model of Water-Rich Mudstone Under Cyclic Loading - Cheng-hua Shi; Zu-de Ding; Ming-feng Lei; Li-min Peng (Rock Mechanics and Rock Engineering, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Improvement of a gene targeting system for genetic manipulation in Penicillium digitatum - Qian Xu; Cong-yi Zhu; Ming-shang Wang; Xue-peng Sun; Hong-ye Li (Journal of Zhejiang University-SCIENCE B, 2014)

The distribution of four Caragana species is related to their differential responses to drought stress - Xiang-Wen Fang; Neil C. Turner; Jairo A. Palta; Ming-Xi Yu; Tian-Peng Gao; Feng-Min Li (Plant Ecology, 2014)

A novel set pair analysis method based on variable weights for liquefaction evaluation - Ming-Wu Wang; Peng Xu; Jian Li; Kui-Yuan Zhao (Natural Hazards, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Zircon U–Pb and pyrite Re–Os age constraints on pyrite mineralization in the Yinjiagou deposit, China - Ming-Tian Zhu; Lian-Chang Zhang; Guang Wu; Xin-Di Jin; Peng Xiang; Wen-Jun Li (International Geology Review, 2013)

Cytochrome P450 oxidoreductase genetic polymorphisms A503V and rs2868177 do not significantly affect warfarin stable dosage in Han-Chinese patients with mechanical heart valve replacement - Sheng-Lan Tan; Zhi Li; Wei Zhang; Guo-Bao Song; Li-Ming Liu; Juan Peng; Zhao-Qian Liu; Lan Fan; Xiang-Guang Meng; Lian-Sheng Wang; Yao Chen; Xin-Min Zhou; et al. (European Journal of Clinical Pharmacology, 2013)

Green-revertible Chlorina 1 (grc1) is required for the biosynthesis of chlorophyll and the early development of chloroplasts in rice - Jieqin Li; Yihua Wang; Juntao Chai; Lihua Wang; Chunming Wang; Wuhua Long; Di Wang; Yunlong Wang; Ming Zheng; Cheng Peng; Mei Niu; Jianmin Wan (Journal of Plant Biology, 2013)

Synthesis and potential antibacterial activity of new rhodanine-3-acetic acid derivatives - Jing Miao; Chang-Ji Zheng; Liang-Peng Sun; Ming-Xia Song; Li-Li Xu; Hu-Ri Piao (Medicinal Chemistry Research, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Association of TGF-β1 +869C/T promoter polymorphism with susceptibility to autoimmune diseases: a meta-analysis - Li Zhang; Jun-wei Yan; Ying-Xin Wang; Ya-nan Wan; Jian-ping Li; Ping Liu; Bin Xu; Bing-xiang Wang; Wen-jia Peng; Fa-ming Pan; Jing Wang (Molecular Biology Reports, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Characterization and Genome Sequencing of Phage Abp1, a New phiKMV-Like Virus Infecting Multidrug-Resistant Acinetobacter baumannii - Guangtao Huang; Shuai Le; Yizhi Peng; Yan Zhao; Supeng Yin; Lin Zhang; Xinyue Yao; Yinling Tan; Ming Li; Fuquan Hu (Current Microbiology, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Feeding by Whiteflies Suppresses Downstream Jasmonic Acid Signaling by Eliciting Salicylic Acid Signaling - Peng-Jun Zhang; Wei-Di Li; Fang Huang; Jin-Ming Zhang; Fang-Cheng Xu; Yao-Bin Lu (Journal of Chemical Ecology, 2013)

Biochemical characterization of NADP+-dependent isocitrate dehydrogenase from Microcystis aeruginosa PCC7806 - Ming-Ming Jin; Peng Wang; Xue Li; Xiao-Yu Zhao; Lei Xu; Ping Song; Guo-Ping Zhu (Molecular Biology Reports, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Antibacterial nanostructured composite films for biomedical applications: microstructural characteristics, biocompatibility, and antibacterial mechanisms - Fei-Peng Lee; Duen-Jeng Wang; Li-Kai Chen; Chun-Ming Kung; Yi-Chien Wu; Keng-Liang Ou; Chih-Hua Yu (Biofouling, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Physiological responses of Microcystis aeruginosa NIES-843 (cyanobacterium) under the stress of chitosan modified kaolinite (CMK) loading - Jihai Shao; Zhongjie Wang; Yang Liu; Hong Liu; Liang Peng; Xiangdong Wei; Ming Lei; Renhui Li (Ecotoxicology, 2012)

The molecular basis for the inhibition of human cytochrome P450 1A2 by oroxylin and wogonin - Yong-Xian Shao; Peng Zhao; Zhe Li; Ming Liu; Peiqing Liu; Min Huang; Hai-Bin Luo (European Biophysics Journal, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

Streptomyces shenzhenensis sp. nov., a novel actinomycete isolated from mangrove sediment - Huo Hu; Hai-Peng Lin; Qingyi Xie; Lei Li; Xin-Qiang Xie; Ming Sun; Kui Hong (Antonie van Leeuwenhoek, 2011)

Mercury Biomagnification in the Aquaculture Pond Ecosystem in the Pearl River Delta - Zhang Cheng; Peng Liang; Ding-Ding Shao; Sheng-Chun Wu; Xiang-Ping Nie; Kun-Ci Chen; Kai-Bin Li; Ming-Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Single cysteine substitution in Bacillus thuringiensis Cry7Ba1 improves the crystal solubility and produces toxicity to Plutella xylostella larvae - Donghai Peng; Fenshan Wang; Nisha Li; Zhenyu Zhang; Rong Song; Zimin Zhu; Lifang Ruan; Ming Sun (Environmental Microbiology, 2011)
Summary Many Bacillus thuringiensis isolates have no demonstrated toxicity against insects. In this study, a novel holotype crystal protein gene cry7Ba1 was isolated from a ‘non‐insecticidal’ B. thuringiensis strain YBT‐978. The Cry7Ba1 protein showed high toxicity against Plutella xylostella larvae after the crystals were dissolved at pH 12.5, suggesting that the ‘non‐insecticidal’ properties of this protein were due to insolubility in the normal insect midgut pH environment. After the C‐terminal half of Cry7Ba1 was replaced by that of Cry1Ac or Cry1C proteins, the recombinant protein inclusions could be dissolved at pH 9.5, and exhibited high toxicity against P. xylostella larvae. This result proved the insolubility of Cry7Ba1 crystal was determined by the structure of its C‐terminal half. Further, six mutations were constructed by substituting cysteine residues with serine. Solubility studies showed that the crystals from mutants C697S, C834S and C854S could be dissolved at lower pH (10.5, 9.5 and 11.5 respectively). Bioassays showed that crystals from mutant C834S were toxic to P. xylostella larvae. Our discoveries suggest that a single cysteine residue located in the C‐terminal half of the protein determines the solubility and toxicity of some nontoxic crystal proteins. This study provides a strategy to isolate novel insecticidal crystal protein genes from ‘non‐insecticidal’ B. thuringiensis strains.

Aluminum regulates oxalate secretion and plasma membrane H+-ATPase activity independently in tomato roots - Jian Li Yang; Xiao Fang Zhu; You Xiang Peng; Cheng Zheng; Feng Ming; Shao Jian Zheng (Planta, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Cloning of Exo-β-1,3-glucanase Gene from a Marine Yeast Williopsis saturnus and Its Overexpression in Yarrowia lipolytica - Ying Peng; Guang-Lei Liu; Xin-Jun Yu; Xiang-Hong Wang; Li Jing; Zhen-Ming Chi (Marine Biotechnology, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Spartina alterniflora invasion increases soil inorganic nitrogen pools through interactions with tidal subsidies in the Yangtze Estuary, China - Rong Hao Peng; Chang Ming Fang; Bo Li; Jia Kuan Chen (Oecologia, 2011)

Effects of temperature change on water discharge, and sediment and nutrient loading in the lower Pearl River basin based on SWAT modelling - Ying Li; Bao-Ming Chen; Zhong-Gen Wang; Shao-Lin Peng (Hydrological Sciences Journal, 2011)

Differentially Expressed Outer Membrane Proteins of Vibrio alginolyticus in Response to Six Types of Antibiotics - Xiao-Peng Xiong; Chao Wang; Ming-Zhi Ye; Tian-Ci Yang; Xuan-Xian Peng; Hui Li (Marine Biotechnology, 2010)

Fractionation of copper and cadmium and their binding with soil organic matter in a contaminated soil amended with organic materials - Ibrahim Mohamed; Bocar Ahamadou; Ming Li; Changxiu Gong; Peng Cai; Wei Liang; Qiaoyun Huang (Journal of Soils and Sediments, 2010)

A fibrillar form of fibronectin induces apoptosis by activating SHP-2 and stress fiber formation - Chun-Yung Huang; Chi-Ming Liang; Chiao-Li Chu; Jei-Ming Peng; Shu-Mei Liang (Apoptosis, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Involvement of anion exchanger-2 in apoptosis of endothelial cells induced by high glucose through an mPTP-ROS-Caspase-3 dependent pathway - Qi-Ren Huang; Qing Li; Yuan-Hong Chen; Li Li; Li-Li Liu; Shui-Hong Lei; He-Ping Chen; Wei-Jie Peng; Ming He (Apoptosis, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

Intrathecal injection of GluR6 antisense oligodeoxynucleotides alleviates acute inflammatory pain of rectum in rats - Wei-Guang Zhang; Li-Cai Zhang; Zhen-Dan Peng; Yin-Ming Zeng (Neuroscience Bulletin, 2009)

Adsorption of lead(II) from aqueous solution onto Hydrilla verticillata - Ling-zhi Huang; Guang-ming Zeng; Dan-lian Huang; Li-feng Li; Peng-mian Huang; Chang-bin Xia (Biodegradation, 2009)

Prediction of shelled shrimp weight by machine vision - Peng-min Pan; Jian-ping Li; Gu-lai Lv; Hui Yang; Song-ming Zhu; Jian-zhong Lou (Journal of Zhejiang University-SCIENCE B, 2009)

Relationships among Avena species as revealed by consensus chloroplast simple sequence repeat (ccSSR) markers - Wei-Tao Li; Yuan-Ying Peng; Yu-Ming Wei; Bernard R. Baum; You-Liang Zheng (Genetic Resources and Crop Evolution, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

Effect of meal size on excess post-exercise oxygen consumption in fishes with different locomotive and digestive performance - Shi-Jian Fu; Ling-Qing Zeng; Xiu-Ming Li; Xu Pang; Zhen-Dong Cao; Jiang-Lan Peng; Yu-Xiang Wang (Journal of Comparative Physiology B, 2009)

Genes Involved in the Benzoate Catabolic Pathway in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Ming Chen; Wei Lu; Shuying Li; Zixin Peng; Wei Zhang; Shuzhen Ping; Jin Wang; Min Lin (Current Microbiology, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Ranging of Rhinopithecus bieti in the Samage Forest, China. II. Use of Land Cover Types and Altitudes - Dayong Li; Cyril C. Grueter; Baoping Ren; Yongcheng Long; Ming Li; Zhengsong Peng; Fuwen Wei (International Journal of Primatology, 2008)

Expression and secretion of recombinant ZZ–EGFP fusion protein by the methylotrophic yeast Pichia pastoris - Jin-bao Tang; Peng Zhu; Hong-ming Yang; Li-min Sun; Shu-liang Song; Ai-guo Ji (Biotechnology Letters, 2008)

A novel two-step fermentation process for improved arachidonic acid production by Mortierella alpina - Ming-Jie Jin; He Huang; Ai-Hua Xiao; Kun Zhang; Xin Liu; Shuang Li; Chao Peng (Biotechnology Letters, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

BRD7 suppresses the growth of Nasopharyngeal Carcinoma cells (HNE1) through negatively regulating β-catenin and ERK pathways - Cong Peng; Hua Ying Liu; Ming Zhou; Li Ming Zhang; Xiao Ling Li; Shou Rong Shen; Gui Yuan Li (Molecular and Cellular Biochemistry, 2007)

Genetic variation and phylogeographic history of Picea likiangensis revealed by RAPD markers - Xiao-Li Peng; Chang-Ming Zhao; Gui-Li Wu; Jian-Quan Liu (Trees, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Silicon’s organic pool and biological cycle in moso bamboo community of Wuyishan Biosphere Reserve - Zhen-ji Li; Peng Lin; Jian-yuan He; Zhi-wei Yang; Yi-ming Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Codon-modifications and an endoplasmic reticulum-targeting sequence additively enhance expression of an Aspergillus phytase gene in transgenic canola - Ri-He Peng; Quan-Hong Yao; Ai-Sheng Xiong; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2006)

Exploring the diversity of myxobacteria in a soil niche by myxobacteria‐specific primers and probes - Zhi‐Hong Wu; De‐Ming Jiang; Peng Li; Yue‐Zhong Li (Environmental Microbiology, 2006)

Exploring the diversity of myxobacteria in a soil niche by myxobacteria‐specific primers and probes - Zhi‐Hong Wu; De‐Ming Jiang; Peng Li; Yue‐Zhong Li (Environmental Microbiology, 2005)
Summary The diversity of myxobacteria in a soil niche was explored using culture‐dependent and ‐independent methods. Conventional cultivation for bacteriolytic myxobacteria produced six types of myxobacteria, which were identified as two Myxococcus spp., two Corallococcus spp., a Cystobacter sp. and a Nannocysts sp. Hybridization analysis of the soil bacterial 16S rRNA gene library with myxobacteria‐specific probes revealed that myxobacteria accounted for less than 1% in the bacterial community. A Cystobacterineae 16S rRNA genes‐rich library was further established from the soil DNA by polymerase chain reaction amplification with a Cystobacterineae‐specific primer combined with a universal bacterial primer. Screening of the special library using Cystobacterineae‐ and Sorangineae‐specific probes produced approximately 45% and 3% positive signals respectively. Sixty‐four positive clones were randomly selected for sequencing. Except three repeats, the sequences were diverse ranging from 0.3% to 21.3%, and homologous with the known myxobacteria at 77.6–99.8%, including 57 in Cystobacterineae, one close to Nannocystis and three much more distant from the known myxobacteria. The sequences in the Cystobacterineae can further be divided into at least 12 groups, of which most were unreported. The results suggest that myxobacteria in nature are much more diverse than were ever known, even in one soil niche.

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)

Bcl10 protein can act as a transcription activator in yeast - Ming Chen; Ling Yun Li; Yi-Peng Qi (Molecular and Cellular Biochemistry, 2003)

THE CULTURE OF FIBROBLASTS FROM DIAPHRAGM OF GIANT PANDA - Zhi-Ming Han; Da-Yuan Chen; Jin-Song Li; Qing-Yuan Sun; Peng-Yang Wang; Yang Huang; Jun Du (In Vitro Cellular & Developmental Biology - Animal, 2001)